Compound, complex, solid electrolyte comprising same, and all-solid-state battery

By using compounds with specific structures and lithium salts to form a solid electrolyte with high lithium affinity, the problems of low ionic conductivity and lithium dendrite growth in solid polymer electrolytes are solved, thereby improving battery performance and stability and supporting fast charging.

CN121002097APending Publication Date: 2025-11-21LG CHEM LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202480027638.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-20
Filing Date
2024-05-03
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing solid polymer electrolytes have low ionic conductivity, and the growth problem of lithium dendrites on the surface of lithium metal anodes has not been effectively solved, affecting the performance and stability of batteries.

Method used

By using compounds with specific structures and lithium salts, a solid electrolyte with high lithium affinity is formed, which improves ionic conductivity by chelating lithium ions and inhibits the growth of lithium dendrites.

Benefits of technology

It improves the ionic conductivity of the solid electrolyte, suppresses the growth of lithium dendrites, improves battery performance and stability, and supports applications in fast-charging environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention aims to improve the low lithium ion conductivity of a conventional all-solid-state battery and to improve the performance and stability of the conventional all-solid-state battery. The present invention relates to a compound comprising a repeating unit represented by Formula 1 described herein or a lithium salt thereof, a complex comprising the compound and a lithium compound, a solid electrolyte comprising the same, and an all-solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Cross-references to related applications

[0002] This application claims priority to Korean Patent Application No. 10-2023-0057976, filed with the Korean Intellectual Property Office on May 3, 2023; Korean Patent Application No. 10-2023-0057984, filed with the Korean Intellectual Property Office on May 3, 2023; and Korean Patent Application No. 10-2023-0094880, filed with the Korean Intellectual Property Office on July 20, 2023, the disclosures of which are incorporated herein by reference in their entirety. Technical Field

[0003] This invention relates to compounds, composites, solid electrolytes containing the same, and all-solid-state batteries for improving the ionic conductivity of all-solid-state batteries and for suppressing the growth of lithium dendrites on the surface of lithium metal anodes. Background Technology

[0004] High-energy-density lithium-ion batteries, currently mainly used in laptops and smartphones, consist of a positive electrode made of lithium oxide, a carbon-based negative electrode, a separator, and a liquid or solid electrolyte. However, lithium-ion batteries made of flammable liquid electrolytes have stability issues such as leakage, fire, and explosion, and preventing these problems complicates battery design.

[0005] Therefore, in order to solve the problems of such liquid electrolytes, solid electrolytes with non-flammable or flame-retardant properties have been studied. Solid electrolytes can be classified into sulfide electrolytes, oxide electrolytes and polymer electrolytes.

[0006] Sulfide electrolytes have the advantages of high ionic conductivity, low interfacial resistance, and stability over a wide voltage range. However, trace impurities such as moisture can enter the battery and react with the sulfide electrolyte, thereby generating hydrogen sulfide inside the battery. There is also a risk of hydrogen sulfide generation during battery charging and discharging. Therefore, sulfide electrolytes have the problem of poor stability.

[0007] In addition, oxide electrolytes have high chemical stability, but lower ionic conductivity than sulfide electrolytes, and require high-temperature sintering, making it difficult to manufacture large-area batteries.

[0008] Therefore, polymer electrolytes have advantages as solid electrolyte materials due to their low cost, softness, and simple processing. As a result, research on polymer electrolytes has been actively carried out.

[0009] Polymer electrolytes are broadly classified into gel-type and solid-type. Gel-type polymer electrolytes are electrolytes that exhibit conductivity by impregnating a high-boiling-point liquid electrolyte in a polymer film and fixing it together with a lithium salt. They contain a large amount of liquid electrolyte and therefore have ionic conductivity similar to that of pure liquid electrolytes, but still have issues with electrochemical stability.

[0010] On the other hand, solid polymer electrolytes do not contain liquid electrolytes, thus solving stability issues related to leakage, and also have the advantage of high chemical and electrochemical stability. However, since the ionic conductivity of solid polymer electrolytes is lower than that of liquid electrolytes at room temperature, a great deal of research has been conducted to address this issue.

[0011] Currently, the most widely used material for solid polymer electrolytes is polyethylene oxide (PEO), which, despite being a solid, possesses the ability to conduct lithium ions. However, in the case of linear PEO polymer electrolytes, there are problems such as limited chain mobility due to high crystallinity, the inability of a large number of lithium ions to dissociate due to low dielectric constant (5.0), and very low ionic conductivity at room temperature, making it difficult to apply linear PEO polymer electrolytes to lithium secondary batteries.

[0012] (Patent Document 001) JP 1985-069140 A Summary of the Invention

[0013] Technical issues

[0014] One object of the present invention is to provide a compound, a solid electrolyte comprising the same, and an all-solid-state battery for improving the ionic conductivity of the solid electrolyte and for improving the performance and stability of the all-solid-state battery.

[0015] Another object of the present invention is to provide a compound, a solid electrolyte comprising the compound, and an all-solid-state battery for suppressing the growth of lithium dendrites, i.e., dendrites, generated on the surface of a lithium metal anode.

[0016] Technical solution

[0017] This invention provides a compound, a composite, a solid electrolyte comprising the compound, and an all-solid-state battery.

[0018] (1) The present invention provides a compound comprising a repeating unit represented by Formula 1 below or a compound as a lithium salt thereof.

[0019] [Formula 1]

[0020]

[0021] In Equation 1 above,

[0022] X, Y, and Z are each independently selected from one or more of the following formulas a-1, b, and c-1.

[0023] n is an integer from 1 to 100.

[0024] q is an integer from 1 to 100.

[0025] o is an integer from 0 to 100.

[0026] * indicates a connection point or terminal point between repeating units.

[0027] [Formula a-1]

[0028]

[0029] [Formula b]

[0030]

[0031] [Formula c-1]

[0032]

[0033] In the above equations a-1, b, and c-1,

[0034] R1, R2, and R3 are each independently hydrogen, halogen, -CN, -NO2, or substituted or unsubstituted C1-C. 10 Alkyl, substituted or unsubstituted C1-C 10 Alkoxy, substituted or unsubstituted C2-C 10 alkenyl, substituted or unsubstituted C2-C 10 Alkyne groups, -C(=O)R5, -P(=O)(OR5)2, -P(OR5)(OR6), -OP(=O)(OR5)(OR6), -S(=O)R5 or -S(=O)2R5,

[0035] R4 is hydrogen or a substituted or unsubstituted C1-C. 10 alkyl,

[0036] R5 and R6 are each independently hydrogen elements, substituted or unsubstituted C1-C. 10 Alkyl or substituted or unsubstituted C2-C 10 alkenyl,

[0037] L1, L2, and L3 are each independently C1-C that are directly connected or substituted or unsubstituted. 10 Alkylene

[0038] X1 and X2 are each independently hydrogen, halogen, -CN, -NO2, or substituted or unsubstituted C1-C. 10Alkyl or substituted or unsubstituted C6-C 12 Aryl,

[0039] m is an integer from 1 to 40.

[0040] p is an integer from 1 to 200.

[0041] (2) In (1) above, the present invention provides a compound wherein at least one of X, Y and Z comprises the above formula a-1.

[0042] (3) In (1) or (2) above, the present invention provides a compound wherein R2 and R4 are each independently C1-C5 alkyl.

[0043] (4) In any of (1) to (3) above, the present invention provides a compound wherein each of L1, L2 and L3 is independently a C1-C5 alkylene group.

[0044] (5) In any of (1) to (4) above, the present invention provides a compound wherein X1 and X2 are each independently hydrogen or halogen elements.

[0045] (6) In any one of (1) to (5) above, the present invention provides a compound, wherein

[0046] n is an integer from 1 to 20.

[0047] q is an integer from 1 to 20.

[0048] o is an integer from 1 to 20.

[0049] m is an integer from 1 to 10.

[0050] p is an integer from 1 to 50.

[0051] (7) In any of (1) to (6) above, the present invention provides a compound comprising a repeating unit represented by Formula 2 above, which is represented by Formula 1-a or Formula 1-b below.

[0052] [Equation 1-a]

[0053]

[0054] [Equation 1-b]

[0055]

[0056] In equations 1-a and 1-b above,

[0057] n is an integer from 1 to 20.

[0058] q is an integer from 1 to 20.

[0059] o is an integer from 1 to 20.

[0060] (8) In any of (1) to (7) above, the present invention provides a compound wherein the compound contains at least one of the functional groups selected from formulas d to g at at least one terminal site.

[0061] [Formula d]

[0062]

[0063] [Form e]

[0064]

[0065] [Form f]

[0066]

[0067] [Formula g]

[0068]

[0069] In the above equations d to g,

[0070] R7 is hydrogen or a substituted or unsubstituted C1-C. 10 alkyl,

[0071] R8 to R 11 Each is independently a directly connected, substituted, or unsubstituted C1-C 10 Alkylene or -R 12 -OR 13 -,

[0072] R 12 and R 13 Each is independently either directly connected or substituted or unsubstituted C1-C. 10 Alkylene

[0073] * indicates the binding position.

[0074] (9) In (8) above, the present invention provides a compound, wherein

[0075] R8 to R 11 Each is independently a directly linked, fluorine-substituted or unsubstituted C1-C6 alkylene group or -R 12 -OR 13 -,and

[0076] R 12 and R 13 Each is an independent C1-C6 alkylene group that is directly connected or substituted or unsubstituted with fluorine.

[0077] (10) In (8) or (9) above, the present invention provides a compound, wherein the compound is represented by the following formula 1-c.

[0078] [Equation 1-c]

[0079]

[0080] In equation 1-c above,

[0081] n is an integer from 1 to 20.

[0082] q is an integer from 1 to 20.

[0083] o is an integer from 1 to 20.

[0084] (11) In any of (1) to (10) above, the present invention provides a compound wherein the lithium salt comprises a repeating unit represented by the following formula 2.

[0085] [Equation 2]

[0086]

[0087] In equation 2 above,

[0088] X, Y, and Z are each independently selected from one or more of the following formulas a-1, b, and c-1.

[0089] n is an integer from 1 to 100.

[0090] q is an integer from 1 to 100.

[0091] o is an integer from 0 to 100.

[0092] * indicates the connection site or terminal site between repeating units, and

[0093] [Formula a-1]

[0094]

[0095] [Formula b]

[0096]

[0097] [Formula c-1]

[0098]

[0099] In the above equations a-1, b, and c-1,

[0100] R1, R2, and R3 are each independently hydrogen, halogen, -CN, -NO2, or substituted or unsubstituted C1-C.10 Alkyl, substituted or unsubstituted C1-C 10 Alkoxy, substituted or unsubstituted C2-C 10 alkenyl, substituted or unsubstituted C2-C 10 Alkyne group, -C(=O)R5, -P(=O)(OR5)2, -P(OR5)(OR6), -OP(=O)(OR5)(OR6), -S(=O)R5 or -S(=O)2R5, where R4 is hydrogen or a substituted or unsubstituted C1-C group. 10 alkyl,

[0101] R5 and R6 are each independently hydrogen elements, substituted or unsubstituted C1-C. 10 Alkyl or substituted or unsubstituted C2-C 10 alkenyl,

[0102] L1, L2, and L3 are each independently C1-C that are directly connected or substituted or unsubstituted. 10 Alkylene

[0103] X1 and X2 are each independently hydrogen, halogen, -CN, -NO2, or substituted or unsubstituted C1-C. 10 Alkyl or substituted or unsubstituted C6-C 12 Aryl,

[0104] m is an integer from 1 to 40.

[0105] p is an integer from 1 to 200.

[0106] (12) In the above (11), the present invention provides a compound, wherein a compound comprising a repeating unit represented by Formula 2 above is represented by Formula 2-a or Formula 2-b.

[0107] [Equation 2-a]

[0108]

[0109] [Equation 2-b]

[0110]

[0111] In equations 2-a and 2-b above,

[0112] n is an integer from 1 to 20.

[0113] q is an integer from 1 to 20.

[0114] o is an integer from 1 to 20.

[0115] (13) In (11) or (12) above, the present invention provides a compound wherein the compound contains at least one of the functional groups selected from formulas d to g at at least one terminal site.

[0116] [Formula d]

[0117]

[0118] [Form e]

[0119]

[0120] [Form f]

[0121]

[0122] [Formula g]

[0123]

[0124] In the above equations d to g,

[0125] R7 is hydrogen or a substituted or unsubstituted C1-C. 10 alkyl,

[0126] R8 to R 11 Each is independently a directly connected, substituted, or unsubstituted C1-C 10 Alkylene or -R 12 -OR 13 -,

[0127] R 12 and R 13 Each is independently either directly connected or substituted or unsubstituted C1-C. 10 Alkylene

[0128] * indicates the binding position.

[0129] (14) In the above (13), the present invention provides a compound, wherein a compound comprising a repeating unit represented by Formula 2 above is represented by Formula 2-c below.

[0130] [Equation 2-c]

[0131]

[0132] In equation 2-c above,

[0133] n is an integer from 1 to 20.

[0134] q is an integer from 1 to 20.

[0135] o is an integer from 1 to 20.

[0136] (15) The present invention provides a complex comprising a compound according to at least one of (1) to (14) above and a lithium compound.

[0137] (16) In (15) above, the present invention provides a compound wherein the lithium compound is selected from one or more of the following substances: LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10 LiAlCl4, LiAlO4, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, lithium bis(fluorosulfonyl)imide (LiFSI) (LiN(SO2F)2), lithium bisperfluoroethanesulfonylimide (LiBETI) (LiN(SO2CF2CF3)2) and lithium (bis)trifluoromethanesulfonylimide (LiTFSI) (LiN(SO2CF3)2).

[0138] (17) In (15) or (16) above, the present invention provides a complex wherein the complex is represented by one or more of the following formulas 3-a, 4-a and 4-b.

[0139] [Equation 3-a]

[0140]

[0141] [Equation 4-a]

[0142]

[0143] [Equation 4-b]

[0144]

[0145] In equations 3-a, 4-a, and 4-b above,

[0146] n is an integer from 1 to 20.

[0147] q is an integer from 1 to 20.

[0148] o is an integer from 1 to 20.

[0149] (18) The present invention provides a solid electrolyte comprising one or more of the compounds selected from those described in (1) to (14) above and the complexes described in (15) to (17) above.

[0150] (19) In (18) above, the present invention provides a solid electrolyte, the solid electrolyte further comprising a crosslinkable compound.

[0151] (20) The present invention provides an all-solid-state battery comprising a solid electrolyte according to (19) above.

[0152] (21) The present invention provides a compound represented by the following formula A.

[0153] [Formula A]

[0154]

[0155] In equation A above,

[0156] R 21 R 22 and R 23 Each is independently hydrogen, halogen, substituted or unsubstituted C1-C 10 Alkyl, substituted or unsubstituted C1-C 10 Alkoxy, substituted or unsubstituted C2-C 10 Alkenyl or substituted or unsubstituted C2-C 10 alkynyl group,

[0157] R 24 It is either hydrogen or substituted or unsubstituted C1-C 10 alkyl,

[0158] L 21 and L 22 Each is independently either substituted or unsubstituted C1-C 10 Alkylene, -P(=O)(OR) 25 -, -(C=O)-, -(S=O)- or -S(=O)2-,

[0159] X 21 and X 22 Each is independently a halogen element, -NH2, or phosphate ester (-OP(=O)(OR)). 25 )2), Nitrate esters (-ON(=O)(OR) 25 Toluenesulfonate (-OTs), sulfonate (-OS(=O)2R) 25 ) or carboxylic acid ester (-OC(=O)CH3), and

[0160] R 25 C1-C, whether substituted or not 10 Alkyl, substituted or unsubstituted C2-C 10 Alkenyl or substituted or unsubstituted C2-C 10 Alkyne group.

[0161] (22) In (21) above, the present invention provides a compound wherein R 22 R24 and R 25 Each is independently a C1-C5 alkyl group.

[0162] (23) In (21) or (22) above, the present invention provides a compound wherein L 21 and L 22 It is -S(=O)2-.

[0163] (24) In any of (21) to (23) above, the present invention provides a compound wherein X 21 and X 22 Each can be independently represented by hydrogen or -NH2.

[0164] (25) In any of (21) to (24) above, the present invention provides a compound, wherein the compound represented by the above formula A is selected from one or more of the following formulas Aa, Ab and Ac.

[0165] [Formula Aa]

[0166]

[0167] [Formula Ab]

[0168]

[0169] [Form Ac]

[0170]

[0171] (26) The present invention provides a complex comprising the compound according to any one of (21) to (25) above and a lithium compound.

[0172] (27) In the above (26), the present invention provides a complex, wherein the complex is represented by the following formula B.

[0173] [Formula B]

[0174]

[0175] In equation B above,

[0176] R 21 R 22 and R 23 Each is independently hydrogen, halogen, substituted or unsubstituted C1-C 10 Alkyl, substituted or unsubstituted C1-C 10 Alkoxy, substituted or unsubstituted C2-C 10 Alkenyl or substituted or unsubstituted C2-C 10 alkynyl group,

[0177] R 24 It is either hydrogen or substituted or unsubstituted C1-C 10 alkyl,

[0178] L 21 and L 22 Each is independently either substituted or unsubstituted C1-C 10 Alkylene, -P(=O)(OR) 25 -, -(C=O)-, -(S=O)- or -S(=O)2-,

[0179] X 21 and X 22 Each is independently a halogen element, -NH2, or phosphate ester (-OP(=O)(OR)). 25 )2), Nitrate esters (-ON(=O)(OR) 25 Toluenesulfonate (-OTs), sulfonate (-OS(=O)2R) 25 ) or carboxylic acid ester (-OC(=O)CH3),

[0180] R 25 C1-C, whether substituted or not 10 Alkyl, substituted or unsubstituted C2-C 10 Alkenyl or substituted or unsubstituted C2-C 10 alkynyl group, and

[0181] Y - It is selected from one or more of the following substances: halide anions, BF4 - ClO4 - AlCl4 - AlO4 - PF6 - CF3SO3 - CH3CO2 - CF3CO2 - AsF6 - SbF6 - CH3SO3 - bis(fluorosulfonyl)imide (FSI) - (N(SO2F)2) - ), bis(perfluoroethanesulfonyl)imide (BETI) (N(SO2CF2CF3)2 - ) and (bis)trifluoromethanesulfonylimide (TFSI) (N(SO2CF3)2 - ).

[0182] (28) In (26) or (27) above, the present invention provides a complex wherein the complex is selected from one or more of the following formulas: Ba, Bb and Bc.

[0183] [Formula Ba]

[0184]

[0185] [Formula Bb]

[0186]

[0187] [Formula Bc]

[0188]

[0189] (29) The present invention provides a polymer comprising repeating units derived from compounds according to any one of (21) to (25) above, repeating units derived from complexes according to any one of (26) to (28) above, or combinations thereof.

[0190] (30) In (29) above, the present invention provides a polymer wherein the repeating unit derived from the compound according to any one of (21) to (25) above is represented by the following formula Wa or Wb.

[0191] [Formula Wa]

[0192]

[0193] [Formula Wb]

[0194]

[0195] In the above equations Wa and Wb,

[0196] n is an integer from 1 to 300.

[0197] * indicates the connection point between repeating units.

[0198] (31) In (29) above, the present invention provides a polymer wherein the repeating unit derived from the complex according to any one of (26) to (28) above is represented by the following formula Xa or Xb.

[0199] [Form Xa]

[0200]

[0201] [Formula Xb]

[0202]

[0203] In the above equations Xa and Xb,

[0204] Y - It is selected from one or more of the following substances: halide anions, BF4 - ClO4 - AlCl4 - AlO4 - PF6 - CF3SO3 - CH3CO2 - CF3CO2 - AsF6 - SbF6 - CH3SO3 - bis(fluorosulfonyl)imide (FSI) - (N(SO2F)2) - ), bis(perfluoroethanesulfonyl)imide (BETI) (N(SO2CF2CF3)2 - ) and (bis)trifluoromethanesulfonylimide (TFSI) (N(SO2CF3)2 - ),

[0205] n is an integer from 1 to 300.

[0206] * indicates the connection point between repeating units.

[0207] (32) In (29) above, the present invention provides a polymer wherein a combination of repeating units derived from the compound according to any one of (21) to (25) above and repeating units derived from the complex according to any one of (26) to (28) above is represented by the following formula Y or Z.

[0208] [Formula Y]

[0209]

[0210] [Form Z]

[0211]

[0212] In the above equations Y and Z,

[0213] Y - It is selected from one or more of the following substances: halide anions, BF4 - ClO4 - AlCl4 - AlO4 - PF6 - CF3SO3 - CH3CO2 - CF3CO2- AsF6 - SbF6 - CH3SO3 - bis(fluorosulfonyl)imide (FSI) - (N(SO2F)2) - ), bis(perfluoroethanesulfonyl)imide (BETI) (N(SO2CF2CF3)2 - ) and (bis)trifluoromethanesulfonylimide (TFSI) (N(SO2CF3)2 - ),

[0214] n and m are each independent integers from 1 to 300.

[0215] * indicates the connection point between repeating units.

[0216] (33) The present invention provides a solid electrolyte comprising the polymer according to any one of (29) to (32) above.

[0217] Beneficial effects

[0218] According to the present invention, if a compound having a lithium-affinity structure capable of chelating lithium ions and a compound as its lithium salt are applied to an all-solid-state battery, the effect of improving ionic conductivity and ion transference number can be achieved.

[0219] According to the present invention, if a compound with a high lithium-ion transference number and a compound as its lithium salt are applied to an electrolyte, the growth of lithium dendrites generated on the surface of the negative electrode can be suppressed. Detailed Implementation

[0220] The invention will be described in more detail below to facilitate understanding. It should be understood that the words or terms used in this specification and claims should not be construed as having the meanings defined in common dictionaries. It should also be understood that the words or terms should be interpreted as having meanings consistent with their meanings within the context of the prior art and the technical concept of the invention, based on the principle that the inventors can appropriately define the meanings of the words or terms to best interpret the invention.

[0221] The terminology used herein is for describing exemplary embodiments only and is not intended to limit the invention. Unless the context clearly indicates otherwise, singular expressions include plural expressions.

[0222] In this specification, it should be understood that the terms "comprising," "including," or "having" are intended to specify the presence of the stated features, number, steps, elements, or combinations thereof, but do not exclude the presence or addition of more than one other feature, number, step, element, or combination thereof.

[0223] The term "all-solid-state battery" as used in this specification refers to a battery in which all components are solid, as opposed to liquid electrolyte secondary batteries that use liquid electrolytes such as electrolyte solutions, and gel polymer secondary batteries that use polymer electrolytes instead of separators and also use liquid electrolytes.

[0224] In this specification, the term "substituted or unsubstituted" means substituted with one or more substituents selected from deuterium, halogen groups, hydroxyl groups, amino groups, thiols, nitro groups, nitrile groups, silyl groups, and straight-chain or branched C1-C6 alkoxy groups, or not having any substituents.

[0225] Unless otherwise stated, the term "alkyl" as used in this specification may refer to a straight or branched acyclic group having 1 to 20 carbon atoms, 1 to 16 carbon atoms, 1 to 12 carbon atoms, 1 to 8 carbon atoms, or 1 to 6 carbon atoms; a cyclic group having 3 to 20 carbon atoms, 3 to 16 carbon atoms, 3 to 12 carbon atoms, 3 to 8 carbon atoms, or 3 to 6 carbon atoms; or a saturated hydrocarbon group consisting of combinations of these groups.

[0226] Unless otherwise stated, the term "alkenyl" as used in this specification may refer to a straight-chain or branched acyclic group having 2 to 20 carbon atoms, 2 to 16 carbon atoms, 2 to 12 carbon atoms, 2 to 8 carbon atoms, or 2 to 6 carbon atoms, having one or more double bonds; a cyclic group having 3 to 20 carbon atoms, 3 to 16 carbon atoms, 3 to 12 carbon atoms, 3 to 8 carbon atoms, or 3 to 6 carbon atoms, having one or more double bonds; or an unsaturated hydrocarbon group consisting of combinations of these groups.

[0227] Unless otherwise stated, the term "alkynyl" as used in this specification may refer to a straight-chain or branched acyclic group having 2 to 20 carbon atoms, 2 to 16 carbon atoms, 2 to 12 carbon atoms, 2 to 8 carbon atoms, or 2 to 6 carbon atoms, having one or more triple bonds; a cyclic group having 3 to 20 carbon atoms, 3 to 16 carbon atoms, 3 to 12 carbon atoms, 3 to 8 carbon atoms, or 3 to 6 carbon atoms, having one or more triple bonds; or an unsaturated hydrocarbon group consisting of combinations of these groups.

[0228] In this specification, "*" refers to a bonding position, which is the connection site between repeating units or the position where a functional group is bonded at the end. In the case of the end, it can refer to one or more substances selected from the following: hydrogen atom, -CN, -NH2, halogen element, substituted or unsubstituted C1-C. 10 Alkyl, substituted or unsubstituted C1-C 10 Alkoxy, substituted or unsubstituted C2-C 10 Alkenyl or substituted or unsubstituted C2-C 10 Alkyne group.

[0229] compound

[0230] The present invention provides a compound comprising a repeating unit represented by Formula 1 or a compound as a lithium salt thereof.

[0231] [Formula 1]

[0232]

[0233] In Equation 1 above,

[0234] X, Y, and Z are each independently selected from one or more of the following formulas a-1, b, and c-1.

[0235] n is an integer from 1 to 100.

[0236] q is an integer from 1 to 100.

[0237] o is an integer from 0 to 100.

[0238] * indicates a connection point or terminal point between repeating units.

[0239] [Formula a-1]

[0240]

[0241] [Formula b]

[0242]

[0243] [Formula c-1]

[0244]

[0245] In the above equations a-1, b, and c-1,

[0246] R1, R2, and R3 are each independently hydrogen, halogen, -CN, -NO2, or substituted or unsubstituted C1-C. 10 Alkyl, substituted or unsubstituted C1-C 10 Alkoxy, substituted or unsubstituted C2-C 10 alkenyl, substituted or unsubstituted C2-C 10 Alkyne groups, -C(=O)R5, -P(=O)(OR5)2, -P(OR5)(OR6), -OP(=O)(OR5)(OR6), -S(=O)R5 or -S(=O)2R5,

[0247] R4 is hydrogen or a substituted or unsubstituted C1-C. 10 alkyl,

[0248] R5 and R6 are each independently hydrogen elements, substituted or unsubstituted C1-C. 10 Alkyl or substituted or unsubstituted C2-C 10 alkenyl,

[0249] L1, L2, and L3 are each independently C1-C that are directly connected or substituted or unsubstituted. 10 Alkylene

[0250] X1 and X2 are each independently hydrogen, halogen, -CN, -NO2, or substituted or unsubstituted C1-C. 10 Alkyl or substituted or unsubstituted C6-C 12 Aryl,

[0251] m is an integer from 1 to 40.

[0252] p is an integer from 1 to 200.

[0253] Conventional liquid electrolytes are flammable, thus posing safety issues such as fire hazards. Solid electrolytes do not have the leakage problems of liquids, thus exhibiting excellent process stability and can be processed into thin films and membranes, thereby offering excellent process convenience. However, as mentioned above, solid electrolytes have the disadvantage of significantly lower ionic conductivity than conventional liquid electrolytes. Therefore, the inventors have developed a compound having a lithium affinity structure according to the present invention, and a solid electrolyte comprising the compound.

[0254] The compound containing the repeating unit represented by Formula 1 above and its lithium salt are compounds with a lithium-affinity structure capable of chelating lithium ions. The compound containing the repeating unit represented by Formula 1 above and its lithium salt contain a sulfonylimide or an anion of the sulfonylimide in which a proton bound to nitrogen is released, thus exhibiting high affinity for lithium ions when used as a material in a solid electrolyte. Furthermore, in the process of manufacturing a solid electrolyte containing a compound containing the repeating unit represented by Formula 1 above, a proton bound to nitrogen in the sulfonylimide can be released. Additionally, the sulfonylimide anion has a relatively low electron density compared to anions of other organic groups, such as carboxylate groups, resulting in weak electrostatic attraction to lithium ions and thereby increasing the lithium ion transport number in the solid electrolyte. In particular, the aforementioned lithium salt can improve the lithium ion transport number compared to materials obtained by hydrogenating conventional ethylene oxide materials or materials mixed alone with lithium salts, such as PEO mixtures mixed with lithium salts.

[0255] Furthermore, compounds containing repeating units represented by Formula 1 above, and their lithium salts, contain one or more of Formulas a-1, b, and c-1, thereby allowing the electrons of the sulfonamide anion to be delocalized, further improving the ionic conductivity of the solid electrolyte. Additionally, the compounds according to the invention are also used as conventional lithium salts in solid electrolytes, thereby replacing conventional lithium salts and reducing the manufacturing cost of all-solid-state batteries.

[0256] Furthermore, lithium metal anodes, which are attracting much attention as anode materials in next-generation batteries, including conventional solid-state batteries, suffer from long-term problems such as shortened lifespan and side reactions due to the formation of lithium dendrites, i.e., lithium dendritic crystals. Solid electrolytes containing the compounds of this invention have high lithium-ion transference numbers, thereby suppressing dendrite formation and improving battery life. Additionally, lithium dendrite formation accelerates in fast-charging environments, making it difficult to introduce fast charging in conventional lithium metal battery compositions. However, in all-solid-state batteries containing the compounds of this invention, dendrite formation is suppressed, making fast charging feasible. The compounds of this invention can be compounds containing repeating units represented by Formula 1 and their lithium salts, whereby the lithium salt can be a compound containing repeating units represented by Formula 2, described later. In particular, experimental results described later show that the aforementioned lithium salts have relatively high lithium transference numbers, thus more effectively suppressing dendrite formation.

[0257] Furthermore, according to one embodiment of the invention, X, Y, and Z can each independently be one or more selected from formulas a-1, b, and c-1 below, and at least one of X, Y, and Z can include formula a-1. Compounds containing repeating units represented by formula 1 above, and their lithium salts, are ion-conducting polymers and contain a structure with an aromatic ring, wherein an alkoxy group is substituted at a carbon position on the benzene ring, and alkyl groups substituted with sulfonyl groups are located on either side of the adjacent position; therefore, they can have a lithium-affinity structure capable of chelating lithium ions. The present invention provides a compound with lithium-ion conductivity, which can improve the mobility of lithium ions through the above-described lithium-affinity structure, and when this compound is used as a material for a solid electrolyte, it can have the effect of improving ion conductivity.

[0258] In addition, according to one embodiment of the present invention, R2 and R4 can be C1-C5 alkyl groups.

[0259] In addition, according to one embodiment of the present invention, L1, L2 and L3 can be C1-C5 alkylene groups.

[0260] Furthermore, according to one embodiment of the invention, X1 and X2 can each independently be hydrogen or a halogen element, wherein the halogen element can be one or more selected from F, Cl, Br, and I. The compound containing the repeating unit represented by Formula 1 above and its lithium salt can contain an alkylene group substituted with a halogen element, preferably fluorine. If the halogen element is fluorine, the highly electronegative fluorine can delocalize the anion of the adjacent sulfonylimide, thereby reducing the electron density of the sulfonylimide, and consequently, reducing the electrostatic attraction between lithium ions and the solid electrolyte. Therefore, the above-described compound can move dissociated lithium ions in the electrolyte with higher efficiency, thus exhibiting higher ionic conductivity than conventional alkylene oxide polymers, and possessing electrochemical stability even at high voltages when used in all-solid-state batteries.

[0261] In addition, according to one embodiment of the present invention, in Equation 1 above and Equations a-1, b and c-1, it is possible that n is an integer from 1 to 20, q is an integer from 1 to 20, o is an integer from 1 to 20, m is an integer from 1 to 10, and p is an integer from 1 to 50.

[0262] In addition, according to one embodiment of the present invention, a compound comprising a repeating unit represented by Formula 1 above may be represented by Formula 1-a or 1-b below.

[0263] [Equation 1-a]

[0264]

[0265] [Equation 1-b]

[0266]

[0267] In equations 1-a and 1-b above, n is an integer from 1 to 20, q is an integer from 1 to 20, and o is an integer from 1 to 20.

[0268] If a compound containing repeating units represented by Formula 1 above is represented by Formula 1-a or 1-b above, then the compound may have a higher lithium-ion conductivity than polymer materials of conventionally used solid electrolytes.

[0269] According to one embodiment of the invention, the compound may contain one or more functional groups selected from formulas d to g at at least one terminal site.

[0270] [Formula d]

[0271]

[0272] [Form e]

[0273]

[0274] [Form f]

[0275]

[0276] [Formula g]

[0277]

[0278] In the above equations d to g, R7 is hydrogen or a substituted or unsubstituted C1-C. 10 Alkyl, R8 to R 11 Each is independently a directly connected, substituted, or unsubstituted C1-C 10 Alkylene or -R 12 -OR 13 -, R 12 and R 13 Each is independently either directly connected or substituted or unsubstituted C1-C. 10 Alkylene, * indicates the bonding position.

[0279] The compound contains one or more functional groups selected from formulas d to g at at least one of the two ends of the repeating unit. This facilitates the formation of a network between the repeating units in the compound, and the formation of the network can significantly increase the weight-average molecular weight of the polymer. Accordingly, if the compound and its lithium salt are applied to a solid electrolyte, the mechanical strength of the solid electrolyte can be improved.

[0280] Furthermore, according to one embodiment of the present invention, in formulas d to g above, R7 is a C1-C6 alkyl group, and R8 to R... 11 Each is independently a directly linked, fluorine-substituted or unsubstituted C1-C6 alkylene group or -R 12 -OR 13 - and R 12 and R 13 Each of the functional groups is a C1-C6 alkylene group that is directly linked or substituted or unsubstituted with fluorine. Specifically, the functional groups of formulas d to g can be one or more selected from the following substances: acrylates, vinyl groups, isocyanates, and alcohols.

[0281] On the other hand, in the process of polymerizing the compounds contained in the solid electrolyte of the present invention, in addition to the compound and its lithium salt containing a repeating unit represented by Formula 1 above and a compound containing one or more functional groups selected from Formulas d to g located at at least one of the two ends of the repeating unit, a crosslinkable compound may also be included. The crosslinkable compound may be one or more substances selected from the following: polyfunctional acrylates, vinyl groups, isocyanates, and alcohols.

[0282] For example, if the functional group of formula d or e, having an acrylate or vinyl structure, is located at one end of a repeating unit, a crosslinkable compound containing pentaerythritol tetraacrylate (PETA) can be further added to form a network between the repeating units. In this case, the acrylate, vinyl, and PETA contain double bonds, allowing for free radical polymerization between the functional group of formula d or e and the double bonds of the crosslinkable compound.

[0283] Alternatively, for example, if the functional group of formula g with an alcohol structure (-OH) is located at the end of the repeating unit, a crosslinkable compound containing hexamethylene diisocyanate (1,6-hexane diisocyanate) can be added to form a network between the repeating units. Alternatively, if the functional group of formula f with an isocyanate structure (-NCO) is located at the end of the repeating unit, a crosslinkable compound containing glycerol or propane-1,2,3-tricarboxylic acid can be added to form a network between the repeating units. In this case, the -OH group and the -NCO group can form a -NHCOO- structure through addition polymerization.

[0284] In addition, according to one embodiment of the present invention, the compound can be represented by the following formula 1-c.

[0285] [Equation 1-c]

[0286]

[0287] In the above equation 1-c, n is an integer from 1 to 20, q is an integer from 1 to 20, and o is an integer from 1 to 20.

[0288] If the compound, specifically a compound containing repeating units represented by Formula 1, is represented by Formula 1-c above, then the compound can have a higher lithium-ion conductivity than polymer materials of conventionally used solid electrolytes.

[0289] According to one embodiment of the present invention, the lithium salt of the compound comprising the repeating unit represented by Formula 1 above can be a compound comprising the repeating unit represented by Formula 2 below.

[0290] [Equation 2]

[0291]

[0292] In equation 2 above,

[0293] X, Y, and Z are each independently selected from one or more of the following formulas a-1, b, and c-1.

[0294] n is an integer from 1 to 100.

[0295] q is an integer from 1 to 100.

[0296] o is an integer from 0 to 100.

[0297] * indicates the connection point between repeating units.

[0298] [Formula a-1]

[0299]

[0300] [Formula b]

[0301]

[0302] [Formula c-1]

[0303]

[0304] In the above equations a-1, b, and c-1,

[0305] R1, R2, and R3 are each independently hydrogen, halogen, -CN, -NO2, or substituted or unsubstituted C1-C. 10 Alkyl, substituted or unsubstituted C1-C 10 Alkoxy, substituted or unsubstituted C2-C 10 alkenyl, substituted or unsubstituted C2-C 10 Alkyne groups, -C(=O)R5, -P(=O)(OR5)2, -P(OR5)(OR6), -OP(=O)(OR5)(OR6), -S(=O)R5 or -S(=O)2R5,

[0306] R4 is hydrogen or a substituted or unsubstituted C1-C. 10 alkyl,

[0307] R5 and R6 are each independently hydrogen elements, substituted or unsubstituted C1-C. 10 Alkyl or substituted or unsubstituted C2-C 10 alkenyl,

[0308] L1, L2, and L3 are each independently C1-C that are directly connected or substituted or unsubstituted. 10 Alkylene

[0309] X1 and X2 are each independently hydrogen, halogen, -CN, -NO2, or substituted or unsubstituted C1-C. 10 Alkyl or substituted or unsubstituted C6-C 12 Aryl,

[0310] m is an integer from 1 to 40.

[0311] p is an integer from 1 to 200.

[0312] The compound containing the repeating unit represented by Formula 2 above is a lithiated compound containing the repeating unit represented by Formula 1 above, and may have the effect of improving the lithium-ion transference number.

[0313] In addition, according to one embodiment of the present invention, the compound comprising the repeating unit represented by Formula 2 above can be a compound represented by Formula 2-a or 2-b below.

[0314] [Equation 2-a]

[0315]

[0316] [Equation 2-b]

[0317]

[0318] In equations 2-a and 2-b above,

[0319] n is an integer from 1 to 20.

[0320] q is an integer from 1 to 20.

[0321] o is an integer from 1 to 20.

[0322] If a compound containing repeating units represented by Formula 2 above is represented by Formula 2-a or 2-b above, then the compound may have a higher lithium-ion conductivity than polymer materials of conventionally used solid electrolytes.

[0323] According to one embodiment of the invention, the lithium salt compound may contain one or more functional groups selected from formulas d to g at at least one terminal site.

[0324] [Formula d]

[0325]

[0326] [Form e]

[0327]

[0328] [Form f]

[0329]

[0330] [Formula g]

[0331]

[0332] In the above equations d to g,

[0333] R7 is hydrogen or a substituted or unsubstituted C1-C. 10 alkyl,

[0334] R8 to R 11 Each is independently a directly connected, substituted, or unsubstituted C1-C 10 Alkylene or -R 12 -OR 13 -,

[0335] R 12 and R 13 Each is independently either directly connected or substituted or unsubstituted C1-C. 10 Alkylene

[0336] * indicates the binding position.

[0337] In addition, according to one embodiment of the present invention, a compound comprising a repeating unit represented by Formula 2 above can be represented by Formula 2-c below.

[0338] [Equation 2-c]

[0339]

[0340] In the above equation 2-c, n is an integer from 1 to 20, q is an integer from 1 to 20, and o is an integer from 1 to 20.

[0341] If the compound (specifically, a compound containing repeating units represented by Formula 2) is represented by Formula 2-c above, then the compound can have a higher lithium-ion conductivity than polymer materials of conventionally used solid electrolytes.

[0342] complex

[0343] The present invention provides a complex comprising a compound according to the invention and a lithium compound.

[0344] Specifically, the present invention provides a complex comprising one or more compounds selected from compounds of Formula 1 above and their lithium salts, and a lithium compound.

[0345] The complex can be a complex containing repeating units represented by Formula 3 or Formula 4.

[0346] [Formula 3]

[0347]

[0348] [Formula 4]

[0349]

[0350] In equations 3 and 4 above,

[0351] X, Y, and Z are each independently selected from one or more of the following formulas: a-2, b, c-1, and c-2, wherein at least one of X, Y, and Z necessarily includes formula a-2 or c-2.

[0352] n is an integer from 1 to 100.

[0353] q is an integer from 1 to 100.

[0354] o is an integer from 0 to 100.

[0355] * indicates the connection point between repeating units.

[0356] [Equation a-2]

[0357]

[0358] [Formula b]

[0359]

[0360] [Formula c-1]

[0361]

[0362] [Equation c-2]

[0363]

[0364] In the above equations a-2, b, c-1, and c-2,

[0365] R1, R2, and R3 are each independently hydrogen, halogen, -CN, -NO2, or substituted or unsubstituted C1-C. 10 Alkyl, substituted or unsubstituted C1-C 10 Alkoxy, substituted or unsubstituted C2-C 10 alkenyl, substituted or unsubstituted C2-C 10 Alkyne groups, -C(=O)R5, -P(=O)(OR5)2, -P(OR5)(OR6), -OP(=O)(OR5)(OR6), -S(=O)R5 or -S(=O)2R5,

[0366] R4 is hydrogen or a substituted or unsubstituted C1-C. 10 alkyl,

[0367] R5 and R6 are each independently hydrogen elements, substituted or unsubstituted C1-C. 10 Alkyl or substituted or unsubstituted C2-C 10 alkenyl,

[0368] L1, L2, and L3 are each independently C1-C that are directly connected or substituted or unsubstituted.10 Alkylene

[0369] X1 and X2 are each independently hydrogen, halogen, -CN, -NO2, or substituted or unsubstituted C1-C. 10 Alkyl or substituted or unsubstituted C6-C 12 Aryl,

[0370] A - It is selected from one or more of the following substances: halide anions, BF4 - ClO4 - AlCl4 - AlO4 - PF6 - CF3SO3 - CH3CO2 - CF3CO2 - AsF6 - SbF6 - CH3SO3 - bis(fluorosulfonyl)imide (FSI) - (N(SO2F)2) - ), bis(perfluoroethanesulfonyl)imide (BETI) (N(SO2CF2CF3)2 - ) and (bis)trifluoromethanesulfonylimide (TFSI) (N(SO2CF3)2 - ),

[0371] m is an integer from 1 to 40.

[0372] p is an integer from 1 to 200.

[0373] According to one embodiment of the present invention, a composite comprising a repeating unit represented by Formula 3 or Formula 4 may comprise: one or more of a compound comprising a repeating unit represented by Formula 1 or a lithium salt thereof, and a lithium compound, wherein at least one of the compound comprising a repeating unit represented by Formula 1 or a lithium salt thereof is electrostatically bonded to the lithium compound. By further comprising a lithium compound, the composite of the present invention can increase the transport number of lithium ions, thereby improving ionic conductivity, and can achieve the effect of reducing the diffusion resistance of lithium ions, thereby improving the cycle capacity properties of lithium secondary batteries.

[0374] According to one embodiment of the invention, X, Y, and Z are each independently selected from one or more of the following formulas a-2, b, c-1, and c-2, wherein at least one of X, Y, and Z may necessarily include formula a-2 or c-2. L1, L2, and L3 may be C1-C5 alkylene groups, and X1 to X4 may each be independently hydrogen or a halogen element, wherein the halogen element may be selected from one or more of F, Cl, Br, and I. Additionally, it is permissible that n is an integer from 1 to 20, q is an integer from 1 to 20, o is an integer from 1 to 20, m is an integer from 1 to 10, and p is an integer from 1 to 50. The effect produced according to the above definition of substituents is the same as the effect of the compounds containing repeating units represented by formula 1 and their lithium salts.

[0375] Lithium compounds can be represented as Li + Y - The lithium compound anion Y - It is selected from one or more of the following substances: halide anions, BF4 - ClO4 - AlCl4 - AlO4 - PF6 - CF3SO3 - CH3CO2 - CF3CO2 - AsF6 - SbF6 - CH3SO3 - bis(fluorosulfonyl)imide (FSI) - (N(SO2F)2) - ), bis(perfluoroethanesulfonyl)imide (BETI) (N(SO2CF2CF3)2 - ) and (bis)trifluoromethanesulfonylimide (TFSI) (N(SO2CF3)2 - Specifically, the lithium compound anion Y - It can be a halide anion.

[0376] According to one embodiment of the present invention, R2 and R4 can be C1-C5 alkyl groups. In the structures of Formula 3 or Formula 4 above, if R4 is substituted with a C1-C5 alkyl group, such that the complex contains an alkoxy group, the lithium compound can be electrostatically positioned near the alkoxy group. Specifically, the lithium compound can be in the form of Li + Y - Positioning in the form of [form].

[0377] Furthermore, the lithium compound contained in the above-mentioned composite can be present in an amount ranging from 1% to 40% by weight. The composite containing lithium compounds within this range can increase the lithium-ion transference number and reduce battery resistance, thereby improving cycle capacity properties.

[0378] According to one embodiment of the invention, the complex may contain one or more functional groups selected from formulas d to g at at least one terminal site.

[0379] [Formula d]

[0380]

[0381] [Form e]

[0382]

[0383] [Form f]

[0384]

[0385] [Formula g]

[0386]

[0387] In the above equations d to g,

[0388] R7 is hydrogen or a substituted or unsubstituted C1-C. 10 alkyl,

[0389] R8 to R 11 Each is independently a directly connected, substituted, or unsubstituted C1-C 10 Alkylene or -R 12 -OR 13 -,

[0390] R 12 and R 13 Each is independently either directly connected or substituted or unsubstituted C1-C. 10 Alkylene

[0391] * indicates the binding position.

[0392] According to one embodiment of the invention, the complex may be a complex represented by one or more of the following formulas: 3-a, 4-a and 4-b.

[0393] [Equation 3-a]

[0394]

[0395] [Equation 4-a]

[0396]

[0397] [Equation 4-b]

[0398]

[0399] In equations 3-a, 4-a, and 4-b above, n is an integer from 1 to 20, q is an integer from 1 to 20, and o is an integer from 1 to 20.

[0400] If a complex containing repeating units represented by Formula 3 or Formula 4 above is a complex represented by one or more of Formulas 3-a, 4-a, and 4-b above, the complex may have a higher lithium-ion conductivity than polymer materials of conventionally used solid electrolytes.

[0401] Compounds (monomers)

[0402] This invention provides a compound represented by the following formula A.

[0403] [Formula A]

[0404]

[0405] In equation A above,

[0406] R 21 R 22 and R 23 Each is independently hydrogen, halogen, substituted or unsubstituted C1-C 10 Alkyl, substituted or unsubstituted C1-C 10 Alkoxy, substituted or unsubstituted C2-C 10 Alkenyl or substituted or unsubstituted C2-C 10 alkynyl group,

[0407] R 24 It is either hydrogen or substituted or unsubstituted C1-C 10 alkyl,

[0408] L 21 and L 22 Each is independently either substituted or unsubstituted C1-C 10 Alkylene, -P(=O)(OR) 25 -, -(C=O)-, -(S=O)- or -S(=O)2-,

[0409] X 21 and X 22 Each is independently a halogen element, -NH2, or phosphate ester (-OP(=O)(OR)). 25 )2), Nitrate esters (-ON(=O)(OR) 25Toluenesulfonate (-OTs), sulfonate (-OS(=O)2R) 25 ) or carboxylic acid ester (-OC(=O)CH3),

[0410] R 25 C1-C, whether substituted or not 10 Alkyl, substituted or unsubstituted C2-C 10 Alkenyl or substituted or unsubstituted C2-C 10 Alkyne group.

[0411] The compound represented by Formula A can be a monomer. The compound represented by Formula A can be an aromatic ring material, wherein an alkoxy group is substituted at one carbon position of the benzene ring, and alkyl groups substituted with sulfonyl groups are located on either side of the ortho position. Like crown ethers applying the concept of molecular recognition in supramolecular chemistry, these compounds, based on their structural properties capable of chelating with lithium ions and based on structure-specific interactions, can target the Li-ion of the target material. + It exhibits high selectivity. This invention provides a compound with lithium-ion conductivity, which, through the aforementioned lithium-affinity structure, can improve the lithium-ion mobility (lithium-ion transference number). When this compound is used as a material in a solid electrolyte, it can improve ionic conductivity.

[0412] According to one embodiment of the present invention, in formula A above, R 22 R 24 and R 25 It can be a C1-C5 alkyl group.

[0413] According to one embodiment of the present invention, in formula A above, X 21 and X 22 Each can be an independent hydrogen element or -NH2. The compound represented by formula A above can form an ion-conducting polymer as a monomer, and when the compound represented by formula A above contains at least one of the halogen elements such as F, Cl, I and Br or NH2, a condensation reaction can occur between the halogen element and NH2 to form an ion-conducting polymer.

[0414] According to one embodiment of the present invention, in formula A above, L 21 and L 22 It can be -S(=O)2-. Specifically, if the compound represented by formula A above is in L... 21 and L 22 It contains a sulfonyl group, and X 21 and X 22Containing -NH2, the compound represented by Formula A above contains a sulfonylimide or an anion of the sulfonylimide in which the proton bound to nitrogen is released. Therefore, when used as a material for a solid electrolyte, it can have a high affinity for lithium ions. On the other hand, in the process of manufacturing a solid electrolyte containing a compound comprising a repeating unit represented by Formula 1 above, the proton bound to nitrogen in the sulfonylimide can be released. In addition, in this case, the anion of the sulfonylimide has a relatively low electron density compared to the anions of other organic groups, such as carboxylate groups, and therefore the electrostatic attraction with lithium ions is weak, thereby improving the transference number of lithium ions, i.e., the ionic conductivity. Furthermore, if the compound represented by Formula A above contains an alkoxy group, the oxygen of the alkoxy group, together with the two adjacent sulfonyl groups in the ortho position, can chelate with lithium ions, thereby improving lithium affinity. As a result, the lithium ion conductivity of the solid electrolyte using this material can be improved. In particular, the lithium salts described above can improve the lithium-ion transference number compared to materials obtained by hydrogenation of conventional ethylene oxide materials or materials mixed alone with lithium salts, such as PEO mixtures mixed with lithium salts.

[0415] Furthermore, according to one embodiment of the present invention, the compound represented by the above formula A can be one or more compounds selected from the following formulas Aa, Ab and Ac.

[0416] [Formula Aa]

[0417]

[0418] [Formula Ab]

[0419]

[0420] [Form Ac]

[0421]

[0422] If the compound represented by formula A is selected from one or more of formulas Aa, Ab, and Ac, then the compound can have a higher lithium-ion conductivity than the polymer material of conventionally used solid electrolytes.

[0423] Complex (monomer)

[0424] This invention provides a composite comprising a compound represented by formula A above and a lithium compound. By further including a lithium compound, the composite of this invention can increase the transference number of lithium ions, thereby improving ionic conductivity, and can also reduce the diffusion resistance of lithium ions, thereby improving the cycle capacity properties of lithium secondary batteries.

[0425] According to one embodiment of the invention, the complex can be a complex represented by formula B below. In the complex represented by formula B above, the compound represented by formula A above is bonded to the lithium compound by electrostatic attraction.

[0426] [Formula B]

[0427]

[0428] In equation B above,

[0429] R 21 R 22 and R 23 Each is independently hydrogen, halogen, substituted or unsubstituted C1-C 10 Alkyl, substituted or unsubstituted C1-C 10 Alkoxy, substituted or unsubstituted C2-C 10 Alkenyl or substituted or unsubstituted C2-C 10 alkynyl group,

[0430] R 24 It is either hydrogen or substituted or unsubstituted C1-C 10 alkyl,

[0431] L 21 and L 22 Each is independently either substituted or unsubstituted C1-C 10 Alkylene, -P(=O)(OR) 25 -, -(C=O)-, -(S=O)- or -S(=O)2-,

[0432] X 21 and X 22 Each is independently a halogen element, -NH2, or phosphate ester (-OP(=O)(OR)). 25 )2), Nitrate esters (-ON(=O)(OR) 25 Toluenesulfonate (-OTs), sulfonate (-OS(=O)2R) 25 ) or carboxylic acid ester (-OC(=O)CH3),

[0433] R 25 C1-C, whether substituted or not 10 Alkyl, substituted or unsubstituted C2-C 10 Alkenyl or substituted or unsubstituted C2-C 10 alkynyl group, and

[0434] Y - It is selected from one or more of the following substances: halide anions, BF4 - ClO4 - AlCl4 -AlO4 - PF6 - CF3SO3 - CH3CO2 - CF3CO2 - AsF6 - SbF6 - CH3SO3 - bis(fluorosulfonyl)imide (FSI) - (N(SO2F)2) - ), bis(perfluoroethanesulfonyl)imide (BETI) (N(SO2CF2CF3)2 - ) and (bis)trifluoromethanesulfonylimide (TFSI) (N(SO2CF3)2 - ).

[0435] According to one embodiment of the present invention, in formula B above, R 22 R 24 and R 25 It can be a C1-C5 alkyl group. Additionally, in formula B above, L... 21 and L 22 It can be -S(=O)2-, X 21 and X 22 Each can be an independent halogen element or -NH2. The halogen element can be any of F, Cl, I, and Br. The effect produced according to the above definition of substituents is the same as that produced by the compound represented by formula A above.

[0436] Lithium compounds can be represented as Li + Y - The lithium compound anion Y - It can be selected from one or more of the following substances: halide anions, BF4 - ClO4 - AlCl4 - AlO4 - PF6 - CF3SO3 - CH3CO2 - CF3CO2 - AsF6 - SbF6 - CH3SO3 - bis(fluorosulfonyl)imide (FSI) - (N(SO2F)2) - ), bis(perfluoroethanesulfonyl)imide (BETI) (N(SO2CF2CF3)2 - ) and (bis)trifluoromethanesulfonylimide (TFSI) (N(SO2CF3)2 -Specifically, the lithium compound anion Y - It can be a halide anion.

[0437] According to one embodiment of the present invention, in the structure of the above formula B, if R 24 By substituting alkyl groups, the above complex contains an alkoxy group. The lithium compound can then be positioned near the alkoxy group through electrostatic attraction. Specifically, the lithium compound can be in the form of Li... + Y - Positioning in the form of [form].

[0438] Furthermore, the lithium compound contained in the above-mentioned composite can be present in a content of 1% to 75% by weight. If the content of the lithium compound is within the above range, there can be 1 to 4 moles of lithium cations per mole of composite, thereby increasing the lithium ion transference number and reducing the diffusion resistance of lithium ions, thereby improving the cycle capacity properties.

[0439] According to one embodiment of the present invention, the complex may be one or more complexes selected from the formulas Ba, Bb and Bc.

[0440] [Formula Ba]

[0441]

[0442] [Formula Bb]

[0443]

[0444] [Formula Bc]

[0445]

[0446] If the complex represented by formula B is one or more complexes selected from formulas Ba, Bb and Bc, the complex can have a higher lithium-ion conductivity than the polymer materials of conventionally used solid electrolytes.

[0447] polymer

[0448] The present invention provides a polymer comprising repeating units derived from compounds represented by the above formula A, repeating units derived from complexes represented by the above formula B, or combinations thereof.

[0449] According to one embodiment of the invention, both the compound and the complex can be monomers, and the monomers can be polymerized to form a polymer, which is a solid electrolyte material with ionic conductivity. Specifically, the compound represented by formula A and the complex represented by formula B can be used in X... 21 and X 22The position contains a halogen element or -NH2, for example, the halogen element can be one or more of F, Cl, I and Br. In this case, the compound represented by formula A above and the complex represented by formula B above can be polymerized by a condensation reaction between the contained halogen element and -NH2 to form a polymer containing sulfonamide.

[0450] In addition, according to one embodiment of the invention, in addition to the repeating units derived from the compound and the complex, the polymer may also contain one or more repeating units derived from fluorine and epoxide monomers.

[0451] According to one embodiment of the invention, the repeating unit derived from the compound can be represented by the following formula Wa or Wb.

[0452] [Formula Wa]

[0453]

[0454] [Formula Wb]

[0455]

[0456] In the above equations Wa and Wb, n is an integer from 1 to 300, and * represents the connection point between repeating units.

[0457] The above formula Wb is a repeating unit derived from the lithium salt of the compound represented by the above formula A, and the compound containing this repeating unit can have the effect of further improving the lithium ion transference number.

[0458] In addition, according to one embodiment of the invention, the repeating unit derived from the complex can be represented by the following formula Xa or Xb.

[0459] [Form Xa]

[0460]

[0461] [Formula Xb]

[0462]

[0463] In the above equations Xa and Xb,

[0464] Y - It is selected from one or more of the following substances: halide anions, BF4 - ClO4 - AlCl4 - AlO4 - PF6 - CF3SO3 - CH3CO2 -CF3CO2 - AsF6 - SbF6 - CH3SO3 - bis(fluorosulfonyl)imide (FSI) - (N(SO2F)2) - ), bis(perfluoroethanesulfonyl)imide (BETI) (N(SO2CF2CF3)2 - ) and (bis)trifluoromethanesulfonylimide (TFSI) (N(SO2CF3)2 - ),

[0465] n is an integer from 1 to 300.

[0466] * indicates the connection point between repeating units.

[0467] The above formula Xb contains lithiated compounds, and thus can have the effect of further improving the lithium-ion transference number of solid electrolytes.

[0468] In addition, according to one embodiment of the present invention, the combination of repeating units derived from the compound and repeating units derived from the complex can be represented by the following formula Y or Z.

[0469] [Formula Y]

[0470]

[0471] [Form Z]

[0472]

[0473] In the above equations Y and Z,

[0474] Y - Selected from one or more of the following substances: halide anions, BF4 - ClO4 - AlCl4 - AlO4 - PF6 - CF3SO3 - CH3CO2 - CF3CO2 - AsF6 - SbF6 - CH3SO3 - bis(fluorosulfonyl)imide (FSI) - (N(SO2F)2) - ), bis(perfluoroethanesulfonyl)imide (BETI) (N(SO2CF2CF3)2 - ) and (bis)trifluoromethanesulfonylimide (TFSI) (N(SO2CF3)2- ),

[0475] n and m are each independent integers from 1 to 300.

[0476] * indicates the connection point between repeating units.

[0477] The above formula Z contains a lithiated compound, and thus can have the effect of further improving the lithium-ion transference number of the solid electrolyte.

[0478] solid electrolyte

[0479] This invention provides a solid electrolyte comprising one or more compounds selected from the compound and the complex. Specifically, the compound may be a compound comprising repeating units represented by Formula 1 or Formula 2, and the complex may be a complex comprising repeating units represented by Formula 3 or Formula 4. Additionally, this invention provides a solid electrolyte comprising the polymer described above. Here, the polymer may comprise repeating units derived from the compound represented by Formula A, repeating units derived from the complex, or a combination thereof. Because the solid electrolyte comprises a polymer having a lithium-affinity structure, the lithium-ion mobility is improved, thereby improving ionic conductivity.

[0480] According to one embodiment of the invention, the solid electrolyte may further comprise a crosslinkable compound, which may be selected from one or more of the following: polyfunctional acrylates, vinyl groups, isocyanates, and alcohols. A network can be formed between the repeating units by free radical polymerization or addition polymerization of the functional groups selected from formulas d to g at at least one of the two ends of the repeating unit and the crosslinkable compound. The content regarding the crosslinkable compound is the same as that described in the compound catalog.

[0481] On the other hand, the present invention mixes a solvent with one or more selected from the compounds and complexes to prepare a mixed solution, and uses the mixed solution to form an ion-conducting polymer electrolyte membrane through a membrane-forming process. The solvent may be one or more selected from: methanol, ethanol, 2-propanol, butanol, 2-ethoxyethanol, isopropanol, ethyl acetate, butyl acetate, acetone, dichloroethane, acetonitrile, tetrahydrofuran, N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-diethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, hexamethylphosphoric triamine, 1,3-dimethyl-2-imidazolium ketone, triethyl phosphate, and γ-butyrolactone. The content of the above solvents can be determined taking into account the viscosity of the mixed solution, etc.

[0482] Furthermore, the film-forming process can be solution casting (solution softening), melt extrusion, calendering, or compression molding; more specifically, it can be solution casting. Solution casting can be performed by coating a single substrate, then separating it and bonding it to the positive and negative electrodes. The substrate can be a glass substrate or a plastic substrate. The plastic substrate can include various plastic films, such as polyethylene terephthalate, polyethylene naphthalate, polypropylene, polyethylene, cellulose 3-acetate, cellulose 2-acetate, alkyl poly(meth)acrylate, poly(meth)acrylate copolymer, polyvinyl chloride, polyvinyl alcohol, polycarbonate, polystyrene, cellophane, polyvinylidene chloride copolymer, polyamide, polyimide, vinyl chloride-vinyl acetate copolymer, polytetrafluoroethylene, and polytrifluoroethylene. The thickness of the carrier is preferably from 5 μm to 150 μm, more preferably from 10 μm to 50 μm. In addition, for coating, methods such as spin coating, dip coating, solvent casting, slot die coating, spray coating, roller coating, extrusion coating, curtain coating, die coating, wire bar coating, and doctor blade coating can be used.

[0483] All-solid-state batteries

[0484] The present invention provides an all-solid-state battery, wherein the all-solid-state battery comprises the above-mentioned solid electrolyte.

[0485] According to one embodiment of the present invention, the all-solid-state battery comprises a positive electrode, a negative electrode (or no negative electrode), and a solid electrolyte layer disposed between the positive and negative electrodes, the solid electrolyte layer comprising a solid electrolyte. The all-solid-state battery according to the present invention exhibits a small decrease in ionic conductivity and low electronic conductivity of the solid electrolyte contained therein, thereby resulting in excellent initial efficiency, lifetime properties, and output properties. In this case, the all-solid-state battery of the present invention can be manufactured using methods known in the art. For example, the all-solid-state battery can be manufactured by stacking and pressing such that the solid electrolyte layer exists between the positive and negative electrodes.

[0486] (1) Positive electrode

[0487] The positive electrode can be manufactured by coating a positive electrode slurry containing positive electrode active materials, binders, conductive materials and solvents onto a positive electrode current collector.

[0488] There are no particular restrictions on the positive electrode current collector, as long as it is conductive and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel with a surface treatment of carbon, nickel, titanium, silver, etc. can be used. In addition, fine irregularities can be formed on the surface of the positive electrode current collector to improve the adhesion of the positive electrode active material, and the positive electrode current collector can be used in various forms such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.

[0489] The positive electrode active material is a compound capable of reversibly inserting and extracting lithium. Specifically, it may include lithium metal oxides, which contain lithium and one or more metals such as cobalt, manganese, nickel, and aluminum. More specifically, the lithium metal oxides may be lithium manganese oxides (e.g., LiMnO2, LiMn2O4, etc.), lithium cobalt oxides (e.g., LiCoO2, etc.), lithium nickel oxides (e.g., LiNiO2, etc.), lithium nickel manganese oxides (e.g., LiNi 1-Y Mn Y O2 (where 0 < Y < 1), LiMn 2-z Ni z O4 (where 0 < Z < 2), etc.), lithium nickel cobalt oxides (e.g., LiNi 1-Y1 Co Y1 O2 (where 0 ≤ Y1 < 1), etc.), lithium manganese cobalt oxides (e.g., LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2-z1 Co z1 O4 (where 0 < Z1 < 2), etc.), lithium nickel manganese cobalt oxides (e.g., Li(Ni p Co q Mn r1 )O2 (where 0 < p < 1, 0 < q < 1, 0 < r1 < 1 and p + q + r1 = 1) or Li(Ni p1 Co q1 Mn r2 )O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2 and p1 + q1 + r2 = 2), etc.), or lithium nickel cobalt transition metal (M) oxides (e.g., Li(Ni p2 Co q2 Mn r3 [[ID=​​​​​​​​​​​​​​​​O2, Li(Ni) 0.5 Mn 0.3 Co 0.2 O2, Li(Ni) 0.7 Mn 0.15 Co 0.15 O2, Li(Ni) 0.8 Mn 0.1 Co 0.1 (e.g., O2), or lithium nickel cobalt aluminum oxide (e.g., Li(Ni) 0.8 Co 0.15 Al 0.05 (O2, etc.), and when considering the significant improvement effect caused by controlling the type and content ratio of the constituent elements that form lithium metal oxides, lithium metal oxides can be Li(Ni) 0.6 Mn 0.2 Co 0.2 O2, Li(Ni) 0.5 Mn 0.3 Co 0.2 O2, Li(Ni) 0.7 Mn 0.15 Co 0.15 O2, Li(Ni) 0.8 Mn 0.1 Co 0.1 O2, etc., and any one of them or a mixture of two or more of them can be used.

[0491] Based on the total weight of solids other than solvents in the cathode slurry, the content of cathode active material can be 60% or more by weight, 70% or more by weight, 80% or more by weight, or 99% or less by weight or 98% or less by weight.

[0492] Adhesives are components used to facilitate the bonding between conductive materials, active materials, and current collectors. Examples of adhesives may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and various copolymers thereof.

[0493] Typically, based on the total weight of solids other than solvents in the cathode slurry, the binder content can be from 1% to 20% by weight, preferably from 1% to 15% by weight, and more preferably from 1% to 10% by weight.

[0494] Conductive materials are components used to further improve the conductivity of positive electrode active materials.

[0495] There are no particular restrictions on the conductive materials, as long as they are conductive and do not cause chemical changes in the battery. Examples of materials that can be used include: graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermally cracked carbon black; conductive fibers such as carbon fibers and metal fibers; fluorocarbons; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0496] Typically, based on the total weight of solids other than solvents in the positive electrode slurry, the content of conductive material can be above 1% by weight, below 20% by weight, below 15% by weight, or below 10% by weight.

[0497] The solvent may include an organic solvent, such as N-methyl-2-pyrrolidone (NMP), and may be used in an amount that achieves a preferred viscosity when the positive electrode active material and selective binders, conductive materials, etc., are included. For example, the solvent content may be such that the concentration of the solids containing the positive electrode active material and selective binders and conductive materials is 50% by weight or more, 60% by weight or more, 70% by weight or more, 95% by weight or less, 90% by weight or less, or 85% by weight or less.

[0498] (2) Negative electrode

[0499] For example, the negative electrode can be manufactured by coating a negative electrode slurry containing negative electrode active material, binder, conductive material, solvent, etc. onto a negative electrode current collector, or a graphite electrode made of carbon (C) or lithium metal itself with a thickness of less than 50 μm can be used as the negative electrode, or the negative electrode can be eliminated without a negative electrode.

[0500] For example, if the negative electrode is manufactured by coating a negative electrode slurry onto a negative electrode current collector, the thickness of the negative electrode current collector is typically from 3 μm to 500 μm. There are no particular limitations on the negative electrode current collector, as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., aluminum-cadmium alloys, etc., can be used. Furthermore, as in the case of the positive electrode current collector, fine irregularities can be formed on the surface of the negative electrode current collector to improve the adhesion of the negative electrode active material, and the negative electrode current collector can be used in various forms such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.

[0501] Examples of negative electrode active materials may include one or more of the following: natural graphite, artificial graphite, carbonaceous materials; metals (Me), such as lithium-containing titanium oxide (LTO), Si, SiO2. xSn, Li, Zn, Mg, Cd, Ce, Ni, or Fe; alloys composed of metals (Me); oxides of metals (MeO) x ); and metal (Me) and carbon composites. Silicon-based anode active materials, including silicon (Si) and silicon oxide (SiO2), can be used as anode active materials. x Silicon alloys, etc.; or lithium metal. In the case of silicon-based anode active materials, a thin and stable SEI layer containing siloxane bonds is formed, which can further improve the high-temperature stability and lifespan properties of the battery.

[0502] Alternatively, in the case of lithium metal, it can be conventional lithium metal, including lithium metal or lithium alloys (e.g., alloys of lithium with metals such as aluminum, zinc, bismuth, cadmium, antimony, silicon, lead, tin, gallium, or indium). The lithium metal anode active material can be in the form of a foil, and by depositing the lithium metal anode active material on one side of the anode current collector, the lithium metal anode active material can form a separate layer relative to the anode current collector.

[0503] Based on the total weight of solids other than solvents in the negative electrode slurry, the content of negative electrode active material can be 60% or more by weight, 70% or more by weight, 80% or more by weight, or 99% or less by weight or 98% or less by weight.

[0504] Adhesives are components used to facilitate the bonding between conductive materials, active materials, and current collectors. Examples of adhesives may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and various copolymers thereof.

[0505] Typically, based on the total weight of solids other than solvents in the negative electrode slurry, the binder content can be above 1% by weight, below 20% by weight, below 15% by weight, or below 10% by weight.

[0506] Conductive materials are components used to further improve the conductivity of the negative electrode active material. There are no particular restrictions on conductive materials, as long as they are conductive and do not cause chemical changes in the battery. Examples of conductive materials that can be used include: graphite, such as natural or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermally cracked carbon black; conductive fibers, such as carbon fibers and metal fibers; fluorocarbons; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and conductive materials, such as polyphenylene derivatives, etc.

[0507] Based on the total weight of solids other than solvents in the negative electrode slurry, the content of conductive material can be more than 1% by weight, less than 20% by weight, less than 15% by weight, or less than 10% by weight.

[0508] The solvent may contain water or an organic solvent such as N-methyl-2-pyrrolidone (NMP), and may be used in an amount that achieves a preferred viscosity when the negative electrode active material, as well as selective binders and conductive materials, are included. For example, the solvent content may be such that the concentration of the solids containing the negative electrode active material, as well as selective binders and conductive materials, is 50% by weight or more, 60% by weight or more, 70% by weight or more, 95% by weight or less, 90% by weight or less, or 85% by weight or less.

[0509] When using the metal itself as the negative electrode, the metal thin film itself can be used as the negative electrode, or the negative electrode can be manufactured by physically bonding, rolling, or depositing the metal onto the negative electrode current collector. The deposition method can be electrical phase deposition or chemical vapor deposition.

[0510] For example, the metal film itself or the metal bonded / rolled / deposited on the negative electrode current collector can be one or more metals selected from lithium (Li), nickel (Ni), tin (Sn), copper (Cu) and indium (In), or an alloy of two of these metals.

[0511] (3) Solid electrolyte layer

[0512] In addition to the solid electrolyte comprising the compound according to the invention, the solid electrolyte layer may also comprise an adhesive.

[0513] Adhesives are components used to facilitate the bonding between solid electrolyte particles. Examples of adhesives may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and various copolymers thereof.

[0514] Based on the total weight of the solid electrolyte layer, the adhesive content can be above 0.1% by weight, below 5% by weight, below 3% by weight, or below 2% by weight.

[0515] This invention provides a battery module comprising an all-solid-state battery as a unit cell and a battery pack comprising the battery module. The battery module and battery pack contain secondary batteries with high capacity, high rate performance, and good cycle characteristics, and therefore can be used as a power source for medium to large-sized devices selected from electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems.

[0516] The embodiments of the present invention will be described in detail below to enable those skilled in the art to readily implement the invention. However, the invention can be implemented in many different ways, and the following examples are for illustrative purposes only to aid in understanding the invention and do not limit its scope. It will be apparent to those skilled in the art that various changes and modifications can be made without departing from the scope and spirit of this specification, and such changes and modifications naturally fall within the scope of the claims herein.

[0517] Synthesis example 1

[0518] Preparation of compounds represented by formula a-1-1

[0519] A solution obtained by mixing 1 equivalent of 4-methylanisole, 1.3 equivalents of p-formaldehyde, and 50 equivalents of HCl (6 N aqueous solution) was heated and stirred at 80 °C for 5 hours. The solution was then cooled to room temperature, and the precipitate was separated and dried under reduced pressure to obtain a crude material. The crude material was purified by silica gel column chromatography to obtain 1,3-bis(chloromethyl)-2-methoxy-5-methylbenzene as a primary intermediate.

[0520] An acetonitrile (ACN) / H2O solution containing 2 equivalents of Na2S2O4 and 4 equivalents of NaHCO3 was added to a three-necked round-bottom flask (RBF) and stirred. The primary intermediate material was added dropwise to the stirred material at 45°C. The reaction was terminated after confirmation of complete conversion by thin-layer chromatography (TLC). After the reaction was complete, stirring was stopped, and the aqueous layer was separated from the phase-separated mixture. Water was removed from the aqueous layer using a rotary evaporator under high temperature and reduced pressure to obtain the salt material. The salt material was completely dissolved in a small amount of water and then added dropwise to MeOH to obtain a precipitate. The precipitate was dispersed in a dichloroethane (DCE) solution, and 3 equivalents of PCl5 were added. The mixture was stirred under reflux for approximately 12 hours, and the resulting crude solution was filtered to remove residual salts. The obtained filtered DCE solution was washed with H2O and then dried with MgSO4 to remove the solvent, resulting in (2-methoxy-5-methyl-1,3-phenylene)dimethylsulfonyl chloride as a compound represented by the following formula a-1-1.

[0521] [Formula a-1-1]

[0522]

[0523] The synthesis of the compound represented by formula a-1-1 is achieved through 1 The 1H-NMR spectrum (Bruker, AVANCE NEO) confirmed the compound represented by formula a-1-1 above. 1 The H-NMR data are as follows.

[0524] 1 ¹H-NMR (400 MHZ. d6-dimethyl sulfoxide): δ(ppm) = 6.99(s, 2H), 4.67(s, 4H), 3.78(s, 3H), 2.17(s, 3H)

[0525] Synthesis example 2

[0526] Preparation of the compound represented by formula b-1

[0527] An ACN / H2O solution containing 2 equivalents of Na2S2O4 and 4 equivalents of NaHCO3 was added to a three-necked round-bottom flask (RBF) and stirred. 1,4-Bromooctafluorobutane was then added dropwise to the stirred mixture at 45°C. 19 After FNMR confirmation of the conversion, the reaction was terminated. Once the reaction was complete, stirring was stopped, and the aqueous layer was separated from the phase-separated mixture. Water was removed from the aqueous layer using a rotary evaporator under high temperature and reduced pressure to obtain the salt material. The salt material was completely dissolved in a small amount of water and then added dropwise to MeOH to obtain a precipitate. The precipitate was dispersed in a dichloroethane (DCE) solution, and 3 equivalents of PCl5 were added. The mixture was stirred under reflux for approximately 12 hours, and the resulting crude solution was filtered to remove residual salts. The obtained filtered DCE solution was washed with H₂O and then dried with MgSO₄ to remove the solvent, resulting in 1,1,2,2,3,3,4,4-octafluorobutane-1,4-disulfonyl dichloro, represented by formula b-1.

[0528] [Formula b-1]

[0529]

[0530] The synthesis of the compound represented by formula b-1 is achieved through 19 F-NMR spectrum (Bruker, AVANCE NEO) confirmed. The compound represented by formula b-1 above... 19 The F-NMR data are as follows.

[0531] 19 F-NMR (400 MHZ. d6-dimethyl sulfoxide): δ(ppm) = -104.2(t, 13Hz, 4F), -118.8(t, J = 12Hz, 4F)

[0532] Synthesis example 3

[0533] Preparation of compounds represented by formula c-1-1

[0534] A tetrahydrofuran (THF) solution containing 1 equivalent of polyethylene glycol (number average molecular weight: 200) was added to a three-necked round-bottom flask (RBF), and then 3 equivalents of NaH were dissolved in the solution while stirring. A THF solution containing 1,3-propanesulfonyl lactone was added dropwise to the stirred material at 45°C. The mixture was stirred under reflux heating conditions. 1 After confirming the transformation was complete by ¹H NMR, the solution was cooled to room temperature. Methanol (MeOH) was then added to quench any remaining NaH. The solvent was removed under reduced pressure using a rotary evaporator to obtain a crude material. The crude material was washed and purified with hexane and diethyl ether to obtain poly(ethylene glycol) bis(propane-1-sulfonate) as a primary intermediate.

[0535] The primary intermediate material was dispersed in dichloromethane (DCM) solvent, and then 3 equivalents of PCl5 were added. The mixture was stirred at 40°C for about 12 hours to obtain a crude material. After removing the solvent from it using a rotary evaporator under reduced pressure, the crude material was washed and purified with hexane and diethyl ether to obtain poly(ethylene glycol) bis(propane-1-sulfonyl sodium chloride) as a secondary intermediate material.

[0536] Under a nitrogen atmosphere, 7 equivalents of an aqueous solution of NH4OH were added to a three-necked RBF, and the mixture was stirred at room temperature. The secondary intermediate material was dispersed in acetonitrile, and the dispersion was slowly added to the stirred material over 7 hours. The solution was then stirred at 40°C for approximately 12 hours. Water was subsequently added, and the mixture was extracted several times with ethyl acetate. The organic layer was dried with Na2SO4, and the solvent was removed by rotary evaporation under reduced pressure. The organic layer was then washed and purified with diethyl ether and dried to obtain poly(ethylene glycol) bis(propane-1-sulfonamide) as a compound represented by formula c-1-1.

[0537] [Equation c-1-1]

[0538]

[0539] The synthesis of the compound represented by formula c-1-1 is achieved through 1 The 1H-NMR spectrum (Bruker, AVANCE NEO) confirmed the compound represented by formula c-1-1 above. 1 The H-NMR data are as follows.

[0540] 1¹H-NMR (500 MHZ. d6-dimethyl sulfoxide): δ (ppm) = 6.87 (broad S, 4H), 3.43 (m, 23H), 3.03 (m, 4H), 1.89 (m, 4H)

[0541] Synthesis example 4

[0542] Preparation of the compound represented by formula d-1

[0543] One equivalent of potassium 3-sulfonyl methacrylate (TCI), 0.1 equivalents of DMF, and tetrahydrofuran (THF) were added to a single-necked round-bottom flask (RBF), and 5.5 equivalents of thionyl chloride were slowly added dropwise while stirring. After 3 hours, the reaction was complete, then quenched with water, and extracted three times with dichloromethane (DCM) to obtain the organic layer. The solvent was removed from the organic layer using a rotary evaporator under reduced pressure to obtain 3-(chlorosulfonyl)propyl methacrylate as a compound represented by formula d-1.

[0544] [Equation d-1]

[0545]

[0546] The synthesis of the compound represented by formula d-1 is achieved through 1 The 1H-NMR spectrum (Bruker, AVANCE NEO) confirmed the presence of the compound represented by formula d-1 above. 1 The H-NMR data are as follows.

[0547] 1 ¹H-NMR (500 MHZ. d6-dimethyl sulfoxide): δ(ppm) = 6.13–5.63 (s, 2H), 4.34 (m, 2H), 3.79 (m, 2H), 2.45 (m, 2H), 1.96 (s, 3H)

[0548] Synthesis example 5

[0549] Preparation of compounds represented by formula Aa

[0550] A solution obtained by mixing 1 equivalent of 4-methylanisole, 1.3 equivalents of p-formaldehyde, and 50 equivalents of HCl (6 N aqueous solution) was heated and stirred at 80 °C for 5 hours. The solution was then cooled to room temperature, and the precipitate was separated and dried under reduced pressure to obtain a crude material. The crude material was purified by silica gel column chromatography to obtain 1,3-bis(chloromethyl)-2-methoxy-5-methylbenzene as a primary intermediate.

[0551] An acetonitrile (ACN) / H2O solution containing 2 equivalents of Na2S2O4 and 4 equivalents of NaHCO3 was added to a three-necked round-bottom flask (RBF) and stirred. The primary intermediate material was added dropwise to the stirred material at 45°C. The reaction was terminated after confirmation of complete conversion by thin-layer chromatography (TLC). After the reaction was complete, stirring was stopped, and the aqueous layer was separated from the phase-separated mixture. Water was removed from the aqueous layer using a rotary evaporator under high temperature and reduced pressure to obtain the salt material. The salt material was completely dissolved in a small amount of water and then added dropwise to MeOH to obtain a precipitate. The precipitate was dispersed in a dichloroethane (DCE) solution, and 3 equivalents of PCl5 were added. The mixture was stirred under reflux for approximately 12 hours, and the resulting crude solution was filtered to remove residual salts. The filtered DCE solution was washed with H2O and then dried with MgSO4 to remove the solvent, resulting in (2-methoxy-5-methyl-1,3-phenylene) dimethylsulfonyl chloride as a compound represented by the following formula Aa (the same as the compound represented by formula a-1-1 prepared in Synthesis Example 1 above).

[0552] [Formula Aa]

[0553]

[0554] The synthesis of compounds represented by formula Aa is achieved through... 1 The 1H-NMR spectrum (Bruker, AVANCE NEO) confirmed the presence of compounds represented by Aa above. 1 The H-NMR data are as follows.

[0555] 1 ¹H-NMR (500 MHZ. d6-dimethyl sulfoxide): δ(ppm) = 6.99(s, 2H), 4.67(s, 4H), 3.78(s, 3H), 2.17(s, 3H)

[0556] Synthesis example 6

[0557] Preparation of compounds represented by formula Ab

[0558] Under a nitrogen atmosphere, 5 equivalents of NH3 (7 M in MeOH) were added to a three-necked RBF, and the mixture was stirred at room temperature. 1 equivalent of the compound represented by formula Aa prepared in Synthetic Example 1 above was dispersed in acetonitrile, and the dispersion was slowly added to the stirred material over 7 hours. The solution was then stirred at 40°C for approximately 12 hours. Water was subsequently added, and the mixture was extracted several times with ethyl acetate. The organic layer was dried with Na2SO4, and the solvent was removed by rotary evaporation under reduced pressure. The organic layer was then washed and purified with diethyl ether and dried to obtain (2-methoxy-5-methyl-1,3-phenylene)dimethylsulfonamide as the compound represented by formula Ab.

[0559] [Formula Ab]

[0560]

[0561] The synthesis of compounds represented by formula Ab is achieved through 1 The 1H-NMR spectrum (Bruker, AVANCE NEO) confirmed the presence of the compound represented by the above Ab. 1 The H-NMR data are as follows.

[0562] 1 ¹H-NMR (500 MHZ. d6-dimethyl sulfoxide): δ (ppm) = 7.12 (broad s, 4H), 6.98 (s, 2H), 4.35 (s, 4H), 3.78 (s, 3H), 2.17 (s, 3H)

[0563] Synthesis Example 7

[0564] Preparation of compounds represented by formula Ac

[0565] Under a nitrogen atmosphere, 1 equivalent of NH3 (7 M in MeOH) was added to a three-necked RBF, and the mixture was stirred at room temperature. 1 equivalent of the compound represented by formula Ab prepared in Synthetic Example 2 above was dispersed in acetonitrile, and the dispersion was slowly added to the stirred material over 1 hour, followed by stirring the solution at room temperature for approximately 24 hours. Water was then added, and the mixture was extracted several times with ethyl acetate. The organic layer was dried with Na2SO4, and the solvent was removed from it using a rotary evaporator under reduced pressure. The organic layer was then washed and purified with diethyl ether and dried to obtain (2-methoxy-5-methyl-3-aminosulfonylmethyl)phenyl)methanesulfonyl chloride as the compound represented by formula Ac.

[0566] [Form Ac]

[0567]

[0568] The synthesis of compounds represented by formula Ac is achieved through 1 The 1H-NMR spectrum (Bruker, AVANCE NEO) confirmed the presence of the compound represented by Ac above. 1 The H-NMR data are as follows.

[0569] 1 ¹H-NMR (500 MHZ, d6-dimethyl sulfoxide): δ (ppm) = 7.12 (broad s, 2H), 6.97 (s, 2H), 4.67 (s, 2H), 4.35 (s, 2H), 3.78 (s, 3H), 2.16 (s, 3H)

[0570] Synthesis example 8

[0571] Preparation of compounds represented by formula Ba

[0572] Under a nitrogen atmosphere, an acetonitrile solution containing 1 equivalent of the compound represented by formula Aa prepared in Synthetic Example 1 above was stirred. An aqueous solution containing 5 equivalents of lithium bis(trifluoromethyl)sulfonylimide was slowly added to the corresponding mixture over 1 hour, and the solution was stirred at room temperature for approximately 24 hours. Subsequently, water was added, and the mixture was extracted several times with ethyl acetate. The organic layer was dried with Na₂SO₄, and then the solvent was removed from it using a rotary evaporator under reduced pressure. The organic layer was washed and purified with diethyl ether, and then dried to obtain (2-methoxy-5-methyl-1,3-phenylene)dimethylsulfonyl chloride, lithium bis(trifluoromethyl)sulfonylimide, as a compound represented by formula Ba.

[0573] [Formula Ba]

[0574]

[0575] The synthesis of compounds represented by formula Ba is achieved through 1 The 1H-NMR spectrum (Bruker, AVANCE NEO) confirmed the presence of the compound represented by Ba above. 1 The H-NMR data are as follows.

[0576] 1 ¹H-NMR (500 MHZ. d6-dimethyl sulfoxide): δ(ppm) = 7.08(s, 2H), 4.67(s, 4H), 3.90(s, 3H), 2.17(s, 3H)

[0577] Preparation Example 1

[0578] Preparation of compounds represented by formula 1-a

[0579] Three equivalents of triethylamine, one equivalent of the compound represented by formula c-1-1 above, 0.2 equivalents of the compound represented by formula a-1-1 above, and 0.8 equivalents of the compound represented by formula b-1 above were dispersed in a dimethylformamide (DMF) solution and stirred at 120°C for 24 hours. The solution was then cooled to room temperature, and water and dichloromethane were added to obtain a mixture. The mixture was filtered, and the precipitate was separated. The obtained solid material was then washed with methanol and dried under vacuum. The vacuum-dried solid material and three equivalents of ammonia solution (7 M in MeOH, Sigma Aldrich) were dispersed in a dimethylformamide (DMF) solution and stirred at 50°C for 24 hours. The stirred solution was then cooled to room temperature, and dichloromethane was added to obtain a mixture. The mixture was filtered, and the precipitate was separated to obtain the compound represented by formula 1-a below.

[0580] [Equation 1-a]

[0581]

[0582] In the above formula 1-a, n is an integer from 1 to 20, q is an integer from 1 to 20, and o is an integer from 1 to 20.

[0583] The synthesis of the compound represented by formula 1-a above is achieved through... 1 The ¹H NMR spectrum (Bruker, AVANCE NEO) and GPC (Waters, e2695 GPC) confirmed the results. The number-average molecular weight (Mn) was analyzed to be 11200 g / mol, and the PDI was 1.8. The compounds represented by 1-a above... 1 The H-NMR data are as follows.

[0584] 1 ¹H-NMR (500 MHZ, d6-dimethyl sulfoxide): δ(ppm) = 6.99(s, 0.4H), 4.29(s, 0.8H), 3.78(s, 0.6H), 3.43(m, 23H), 3.02(m, 4H), 2.17(s, 0.6H), 1.89(m, 4H)

[0585] 19 F-NMR (470 MHZ. d6-dimethyl sulfoxide): δ(ppm) = -113.2(t, 4F), -119.1(t, 4F)

[0586] Preparation Example 2

[0587] Preparation of compounds represented by formula 1-b

[0588] Three equivalents of triethylamine, one equivalent of the compound represented by formula c-1-1 above, and one equivalent of the compound represented by formula a-1-1 above were dispersed in a dimethylformamide (DMF) solution and stirred at 120°C for 24 hours. The solution was then cooled to room temperature, and water and dichloromethane were added to obtain a mixture. The mixture was filtered, and the precipitate was separated. The obtained solid material was then washed with methanol and dried under vacuum. The vacuum-dried solid material and three equivalents of ammonia solution (7 M in MeOH, Sigma Aldrich) were dispersed in a dimethylformamide (DMF) solution and stirred at 50°C for 24 hours. The stirred solution was then cooled to room temperature, and dichloromethane was added to obtain a mixture. The mixture was filtered, and the precipitate was separated to obtain the compound represented by formula 1-b below.

[0589] [Equation 1-b]

[0590]

[0591] In equation 1-b above, n is an integer from 1 to 20, and q is an integer from 1 to 20.

[0592] The synthesis of the compound represented by formula 1-b above is achieved through... 1 The ¹H NMR spectrum (Bruker, AVANCE NEO) and GPC (Waters, e2695 GPC) confirmed the results. The number-average molecular weight (Mn) was analyzed to be 7100 g / mol, and the PDI was 1.6. The compounds represented by 1-b above... 1 The H-NMR data are as follows.

[0593] 1 ¹H-NMR (500 MHZ, d6-dimethyl sulfoxide): δ(ppm) = 6.99(s, 2H), 4.29(s, 4H), 3.78(s, 3H), 3.43(m, 23H), 2.43(m, 4H), 2.17(s, 3H), 1.89(m, 4H)

[0594] Preparation Example 3

[0595] Preparation of compounds represented by formula 2-a

[0596] Three equivalents of triethylamine, one equivalent of the compound represented by formula c-1-1 above, 0.2 equivalents of the compound represented by formula a-1-1 above, and 0.8 equivalents of the compound represented by formula b-1 above were dispersed in a dimethylformamide (DMF) solution and then stirred at 120°C for 24 hours. The solution was then cooled to room temperature, and water and dichloromethane were added to obtain a mixture, which was then filtered to separate the precipitate. The obtained solid material was then washed with methanol and then dried under vacuum. The vacuum-dried solid material was dispersed in anhydrous DMF, and then 5 equivalents of lithium hydride were slowly added to it while stirring at room temperature for 24 hours. Unreacted lithium hydride was then filtered to obtain a filtrate, which was filtered to separate the precipitate using excess tetrahydrofuran (THF).

[0597] The precipitate obtained by filtration and separation, along with 3 equivalents of ammonia solution (7 M in MeOH, Sigma Aldrich), was dispersed in a dimethylformamide (DMF) solution and then stirred at 50°C for 24 hours. Subsequently, the stirred solution was cooled to room temperature, and dichloromethane was added to obtain a mixture from which the precipitate was filtered and separated to obtain the compound represented by formula 2-a.

[0598] [Equation 2-a]

[0599]

[0600] In equation 2-a above, n is an integer from 1 to 20, q is an integer from 1 to 20, and o is an integer from 1 to 20.

[0601] The synthesis of the compound represented by formula 2-a above is achieved through... 1 The 1H-NMR spectrum (Bruker, AVANCE NEO) and GPC (Waters, e2695 GPC) confirmed the results. The number-average molecular weight (Mn) was analyzed to be 12400 g / mol, and the PDI was 1.9. The compounds represented by 2-a above... 1 The H-NMR data are as follows.

[0602] 1 ¹H-NMR (500 MHZ, d6-dimethyl sulfoxide): δ (ppm) = 6.99 (s, 0.4H), 4.64 (s, 0.4H), 3.78 (s, 0.6H), 3.43 (m, 23H), 3.32 (m, 4H), 2.17 (s, 0.6H), 1.89 (m, 4H)

[0603] 19F-NMR (470 MHZ. d6-dimethyl sulfoxide): δ(ppm) = -114.1(t, 4F), -119.1(t, 4F)

[0604] Preparation Example 4

[0605] Preparation of compounds represented by formula 2-b

[0606] Three equivalents of triethylamine, one equivalent of the compound represented by formula c-1-1 above, and one equivalent of the compound represented by formula a-1-1 above were dispersed in a dimethylformamide (DMF) solution and stirred at 120°C for 24 hours. The solution was then cooled to room temperature, and water and dichloromethane were added to obtain a mixture, which was then filtered to separate the precipitate. The obtained solid material was then washed with methanol and dried under vacuum. The vacuum-dried solid material was dispersed in anhydrous DMF, and five equivalents of lithium hydride were slowly added to it while stirring at room temperature for 24 hours. Unreacted lithium hydride was then filtered to obtain a filtrate, which was filtered to separate the precipitate using excess tetrahydrofuran (THF).

[0607] The precipitate obtained by filtration and separation, along with 3 equivalents of ammonia solution (7 M in MeOH, Sigma Aldrich), was dispersed in a dimethylformamide (DMF) solution and then stirred at 50°C for 24 hours. Subsequently, the stirred solution was cooled to room temperature, and dichloromethane was added to obtain a mixture. The precipitate was then filtered and separated to obtain the compound represented by formula 2-b.

[0608] [Equation 2-b]

[0609]

[0610] In equation 2-b above, n is an integer from 1 to 20, and q is an integer from 1 to 20.

[0611] The synthesis of the compound represented by formula 2-b above is achieved through... 1 The compound was confirmed by ¹H NMR spectroscopy (Bruker, AVANCE NEO) and GPC (Waters, e2695 GPC). The number-average molecular weight (Mn) was analyzed to be 7300 g / mol, and PDI = 1.6. The compounds represented by 2-b above... 1 The H-NMR data are as follows.

[0612] 1¹H-NMR (500 MHZ, d6-dimethyl sulfoxide): δ(ppm) = 6.99(s, 2H), 4.29(s, 4H), 3.78(s, 3H), 3.43(m, 23H), 3.33(m, 4H), 2.17(s, 3H), 1.89(m, 4H)

[0613] Preparation Example 5

[0614] Preparation of compounds represented by formula 1-c

[0615] After preparing the compound represented by formula 1-a in Preparation Example 1 above, 3 equivalents of TEA, 1 equivalent of the compound represented by formula 1-a, and 2.5 equivalents of the compound represented by formula d-1 were dispersed in a DMF solution and stirred at room temperature for 24 hours. Subsequently, dichloromethane was added to obtain a mixture, from which the mixture was filtered and the precipitate was separated to obtain the compound represented by formula 1-c.

[0616] [Equation 1-c]

[0617]

[0618] In the above equation 1-c, n is an integer from 1 to 20, q is an integer from 1 to 20, and o is an integer from 1 to 20.

[0619] The synthesis of the compound represented by formula 1-c above is achieved through... 1 The ¹H NMR spectrum (Bruker, AVANCE NEO) and GPC (Waters, e2695 GPC) confirmed the results. The number-average molecular weight (Mn) was analyzed to be 15000 g / mol, and the PDI was 1.9. The compounds represented by 1-c above... 1 The H-NMR data are as follows.

[0620] 1 ¹H-NMR (500 MHZ. d6-dimethyl sulfoxide): δ(ppm) = 6.99(s, 0.4H), 6.0(s, 2H), 5.6(s, 2H), 4.29(s, 0.8H), 3.78(s, 0.6H), 3.43(m, 31H), 3.02(m, 8H), 2.1(s, 6.6H), 1.89(m, 4H)

[0621] 19 F-NMR (470 MHZ. d6-dimethyl sulfoxide): δ(ppm) = -113.2(t, 4F), -119.1(t, 4F)

[0622] Preparation Example 6

[0623] Preparation of compounds represented by formula 2-c

[0624] After preparing the compound represented by formula 2-a in Preparation Example 3 above, 3 equivalents of TEA, 1 equivalent of the compound represented by formula 2-a, and 2.5 equivalents of the compound represented by formula d-1 were dispersed in a DMF solution and stirred at room temperature for 24 hours. Subsequently, dichloromethane was added to obtain a mixture, which was then filtered and the precipitate was separated to obtain the compound represented by formula 2-c.

[0625] [Equation 2-c]

[0626]

[0627] The synthesis of the compound represented by formula 2-c above is achieved through... 1 The 1H-NMR spectrum (Bruker, AVANCE NEO) and GPC (Waters, e2695 GPC) confirmed the composition. The number-average molecular weight (Mn) was analyzed to be 15200 g / mol, and the PDI was 1.9. The compounds represented by 2-c above... 1 The H-NMR data are as follows.

[0628] 1 ¹H-NMR (500 MHZ, d6-dimethyl sulfoxide): δ(ppm) = 6.99(s, 0.4H), 6.0(s, 2H), 5.6(s, 2H), 4.64(s, 0.4H), 3.78(s, 0.6H), 3.43(m, 27H), 3.32(m, 8H), 2.4(m, 4H), 2.17(s, 6.6H), 1.89(m, 4H)

[0629] 19 F-NMR (470 MHZ. d6-dimethyl sulfoxide): δ(ppm) = -114.1(t, 4F), -119.1(t, 4F)

[0630] Preparation Example 7

[0631] Preparation of compounds represented by formula W-1

[0632] Three equivalents of triethylamine, one equivalent of the compound represented by formula Aa, and one equivalent of the compound represented by formula Ab were dispersed in a dimethylformamide (DMF) solution and stirred at 120°C for 24 hours. The solution was then cooled to room temperature, and water and dichloromethane were added to obtain a mixture. The mixture was filtered, and the precipitate was separated. The obtained solid material was then washed with methanol and dried under vacuum. The vacuum-dried solid material and three equivalents of ammonia solution (7 M in MeOH, Sigma Aldrich) were dispersed in a dimethylformamide (DMF) solution and stirred at 50°C for 24 hours. The stirred solution was then cooled to room temperature, and dichloromethane was added to obtain a mixture. The mixture was filtered, and the precipitate was separated to obtain the compound represented by formula W-1.

[0633] [Formula W-1]

[0634]

[0635] In the above formula W-1, n is an integer from 1 to 300.

[0636] The synthesis of the compound represented by formula W-1 was confirmed by GPC (Waters, e2695 GPC). The number-average molecular weight (Mn) was analyzed to be 9600 g / mol, and the PDI was 1.9.

[0637] Preparation Example 8

[0638] Preparation of compounds represented by formula X-1

[0639] Under a nitrogen atmosphere, an acetonitrile solution containing 1 equivalent of the compound represented by formula W-1 prepared in Preparation Example 1 above was stirred. An aqueous solution containing 5 equivalents of lithium bis(trifluoromethyl)sulfonylimide was slowly added to the corresponding mixture over 1 hour, and the solution was then stirred at room temperature for approximately 24 hours. Subsequently, water was added, and the mixture was extracted several times with ethyl acetate. The organic layer was dried with Na₂SO₄, and then the solvent was removed from it using a rotary evaporator under reduced pressure. The organic layer was washed and purified with diethyl ether, and then dried to obtain the compound represented by formula X-1.

[0640] [Formula X-1]

[0641]

[0642] In the above formula X-1, n is an integer from 1 to 300.

[0643] The synthesis of the compound represented by formula X-1 was confirmed by GPC (Waters, e2695 GPC). The number-average molecular weight (Mn) was analyzed to be 9900 g / mol, and the PDI was 1.9.

[0644] Preparation Example 9

[0645] Preparation of compounds represented by formula Z-1

[0646] Under a nitrogen atmosphere, the material represented by formula X-1 prepared in Preparation Example 1 was dispersed in anhydrous DMF, and then 5 equivalents of lithium hydride were slowly added to it. The solution was then stirred at room temperature for about 24 hours. Subsequently, the unreacted lithium hydride was filtered to obtain a filtrate, which was filtered from it using an excess of tetrahydrofuran (THF) and the precipitate was separated to obtain the compound represented by formula Z-1.

[0647] [Formula Z-1]

[0648]

[0649] In the above equation Z-1, n and m are each an independent integer from 1 to 300.

[0650] The synthesis of the compound represented by formula Z-1 was confirmed by GPC (Waters, e2695 GPC). The number-average molecular weight (Mn) was 10200 g / mol, and the PDI was 1.9.

[0651] Preparation Example 10

[0652] Preparation of compounds represented by formula Q

[0653] Three equivalents of triethylamine, one equivalent of (2,5-dimethyl-1,3-phenylene)dimethylsulfonamide, and one equivalent of (2,5-dimethyl-1,3-phenylene)dimethylsulfonyl chloride were dispersed in a dimethylformamide (DMF) solution and stirred at 120°C for 24 hours. The solution was then cooled to room temperature, and water and dichloromethane were added to obtain a mixture. The mixture was filtered, and the precipitate was separated. The obtained solid material was then washed with methanol and dried under vacuum to obtain a compound represented by the formula Q.

[0654] [Form Q]

[0655]

[0656] In the above formula Q, n is an integer from 1 to 300.

[0657] The synthesis of the compound represented by the above formula Q was confirmed by GPC (Waters, e2695 GPC). The number-average molecular weight (Mn) was analyzed to be 6100 g / mol, and the PDI was 1.7.

[0658] Example 1

[0659] 3 g of the compound represented by Formula 1-a prepared from Preparation Example 1 was dispersed in 30 mL of N-methyl-2-pyrrolidone solvent to obtain a transparent solution. The transparent solution was then uniformly cast onto a flat glass plate. Subsequently, the solution was dried at 40°C for approximately 12 hours, and then dried in a vacuum oven at 70°C for 24 hours. Through the above steps, an ion-conducting polymer electrolyte membrane with a thickness of 20 μm to 40 μm was prepared.

[0660] Example 2

[0661] An ion-conducting polymer electrolyte membrane was prepared in the same manner as in Example 1 above, except that 3 g of the compound represented by Formula 1-b prepared from Preparation Example 2 was used.

[0662] Example 3

[0663] An ion-conducting polymer electrolyte membrane was prepared in the same manner as in Example 1 above, except that 3 g of the compound represented by Formula 2-a prepared from Preparation Example 3 was used.

[0664] Example 4

[0665] An ion-conducting polymer electrolyte membrane was prepared in the same manner as in Example 1 above, except that 3 g of the compound represented by Formula 2-b prepared from Preparation Example 4 was used.

[0666] Example 5

[0667] Lithium bis(trifluoromethyl)sulfonylimide (EO:Li) + The compound was dissolved in N-methyl-2-pyrrolidone in a molar ratio of 20:1, and then 3 g (20 wt% vs N-methyl-2-pyrrolidone) of the compound represented by formula 1-a prepared from Preparation Example 1 was added to it. The mixture was stirred for 2 hours at room temperature using a top-mounted stirrer. Subsequently, the stirred mixture was sonicated (exposed to ultrasonic conditions) in a bath sonicator for 20 minutes to remove air bubbles, yielding a solution in which the compound represented by formula 3-a was dissolved.

[0668] [Equation 3-a]

[0669]

[0670] In equation 3-a above, n is an integer from 1 to 20, q is an integer from 1 to 20, and o is an integer from 1 to 20.

[0671] Subsequently, the solution was uniformly cast onto a flat glass plate. The solution was then dried at 40°C for approximately 12 hours, and then dried again in a vacuum oven at 70°C for approximately 24 hours to prepare an ion-conducting polymer electrolyte membrane with a thickness of 20 μm to 40 μm.

[0672] Example 6

[0673] An ion-conducting polymer electrolyte membrane containing a compound represented by formula 4-a was prepared in the same manner as in Example 5 above, except that 3 g of the compound represented by formula 2-a prepared from Preparation Example 3 was used instead of the compound represented by formula 1-a.

[0674] [Equation 4-a]

[0675]

[0676] In equation 4-a above, n is an integer from 1 to 20, q is an integer from 1 to 20, and o is an integer from 1 to 20.

[0677] Example 7

[0678] 3 g of the compound represented by Formula 1-c prepared from Preparation Example 5 was dispersed in 30 mL of N-methyl-2-pyrrolidone solvent to obtain a transparent solution, and 0.1 g of AlNB was introduced into it. The solution was then uniformly cast onto a flat glass plate. The solution was then dried at 40°C for approximately 12 hours, and then dried in a vacuum oven at 70°C for 24 hours. Through the above steps, an ion-conducting polymer electrolyte membrane with a thickness of 20 μm to 40 μm was prepared.

[0679] Example 8

[0680] An ion-conducting polymer electrolyte membrane was prepared in the same manner as in Example 7 above, except that 0.1 g of AINB and 0.5 g of PETA were introduced instead of the 0.1 g of AINB introduced in Example 7 above.

[0681] Example 9

[0682] An ion-conducting polymer electrolyte membrane was prepared in the same manner as in Example 7 above, except that 3 g of the compound represented by Formula 2-c prepared from Preparation Example 6 was used.

[0683] Example 10

[0684] An ion-conducting polymer electrolyte membrane was prepared in the same manner as in Example 8 above, except that 3 g of the compound represented by Formula 2-c prepared from Preparation Example 6 was used.

[0685] Example 11

[0686] 3 g of the compound represented by formula W-1 prepared in Preparation Example 7 was dispersed in 30 mL of N-methyl-2-pyrrolidone solvent to obtain a transparent solution. The transparent solution was then uniformly cast onto a flat glass plate. The solution was subsequently dried at 40°C for approximately 12 hours, and then dried in a vacuum oven at 70°C for 24 hours. Through these steps, an ion-conducting polymer electrolyte membrane with a thickness of 20 μm to 40 μm was prepared.

[0687] Example 12

[0688] An ion-conducting polymer electrolyte membrane was prepared in the same manner as in Example 11 above, except that 3 g of the compound represented by formula X-1 prepared from Preparation Example 8 was used.

[0689] Example 13

[0690] An ion-conducting polymer electrolyte membrane was prepared in the same manner as in Example 11 above, except that 3 g of the compound represented by formula Z-1 prepared from Preparation Example 9 was used.

[0691] Comparative Example 1

[0692] Lithium bis(trifluoromethyl)sulfonylimide (EO:Li) + The PEO solution was dissolved in acetonitrile at a molar ratio of 20:1, and then 3 g (20 wt% vs N-methyl-2-pyrrolidone) of PEO was added. The PEO composition was then: PEO (Sigma-Aldrich) with Mw = 100,000 and PEO (Sigma-Aldrich) with MW = 600,000 were mixed at a weight ratio of 9:1. The mixture was stirred for 2 hours at room temperature using a top-mounted stirrer. Subsequently, the stirred mixture was ultrasonically treated (exposed to ultrasonic conditions) for 20 minutes in a bath ultrasonic bath to remove air bubbles, yielding a PEO-LiTFSI solution. The PEO-LiTFSI solution was then drop-added onto an MRF-38 release film using a coating applicator. First, the solution was dried at room temperature for approximately 12 hours, and then vacuum-dried in a vacuum oven at 40°C for 8 hours. Through the above process, PEO-LiTFSI polymer electrolyte membranes with a thickness of 10 μm to 50 μm were prepared.

[0693] Comparative Example 2

[0694] An ion-conducting polymer electrolyte membrane was prepared in the same manner as in Example 11 above, except that 3 g of the compound represented by formula Q prepared from Preparation Example 10 was used.

[0695] Experimental Example 1 – Measurement of Ionic Conductivity

[0696] In a glove box, the polymer electrolyte membranes prepared in the various examples and comparative examples were immersed in an EC / PC (1:1 weight ratio) solvent, and the polymer electrolyte membranes were inserted between two stainless steel electrodes (used as negative and positive electrodes) in a battery case to manufacture a coin battery containing electrode assemblies.

[0697] The impedance of the aforementioned coin cell was measured at room temperature (25°C) using a potentiostat (Biologics SP-200) with an amplitude of 10 mV and a measurement frequency range of 0.1 Hz to 7 MHz. The measured impedance was then substituted into the formula L = I / RS (L = ionic conductivity, I = electrode thickness, R = measured impedance value, S = electrode area) to measure the ionic conductivity. The measured ionic conductivity is shown in Table 1 or 2 below.

[0698] Experimental Example 2 – Measurement of Lithium-ion Transference Number

[0699] In a glove box, the polymer electrolyte membranes prepared in the various examples and comparative examples were immersed in an EC / PC (1:1 weight ratio) solvent. The polymer electrolyte membranes were then inserted between lithium foil electrodes (used as negative and positive electrodes) with a thickness of 200 μm in a battery case and stored at 60°C for about 12 hours to manufacture a coin battery containing electrode assemblies.

[0700] The resistance of the passivation layer of the fabricated coin battery was measured before and after the chronoamperometry experiment using a potentiostat (Biologics SP-200). The measured resistance was then substituted into the formula t. Li+ = I s (△V – I o R o ) / I o (△V – I S R S (ΔV = voltage applied to the battery = 3 mV, I) o =Initial current, I S = Steady-state current, R o =The initial resistance of the passivation layer on the lithium electrode surface, R S =The steady-state resistance of the passivation layer on the lithium electrode surface, used to measure the lithium-ion transport number t Li+The measured lithium-ion mobility numbers are shown in Table 1 or 2 below.

[0701] Experimental Example 3 – Tensile Strength and Tensile Strain

[0702] The tensile strength and tensile strain of the films prepared in Examples 7 to 10 and Comparative Example 1 were measured using a static material testing machine (measuring device) from ZwickiLine, and the results are shown in Table 2 below. Specifically, specimens cut to a width of 10 mm and a length of 30 mm were fixed to the aforementioned measuring device, and the force at which the specimen broke and the change in specimen length were measured while the specimen was stretched at a speed of 5 mm per minute. Tensile strength is the value obtained by dividing the force at which deformation or fracture occurs by the cross-sectional area of ​​the specimen before deformation, and tensile strain is the change in specimen length relative to the applied force.

[0703]

[0704] Referring to Table 1, it can be confirmed that Examples 3 to 6 have higher levels of lithium-ion conductivity and ion transference number compared to Comparative Example 1. Furthermore, it can be confirmed that Examples 1 and 2 also have comparable or higher levels of lithium-ion conductivity and ion transference number compared to Comparative Example 1. The examples include ion-conducting polymers in which lithium-ion-affinity and low-electron-density sulfonamide anions are immobilized in the main chain. These ion-conducting polymers can move dissociated lithium ions in the electrolyte with higher efficiency, thus exhibiting higher ion conductivity and higher ion transference number performance compared to comparative examples containing conventional epoxy alkyl polymers.

[0705] Furthermore, it was confirmed that Example 1, using the compound represented by Formula 1-a, had higher ionic conductivity and a higher ion transference number compared to Example 2, which used the compound represented by Formula 1-b, and Example 3, using the compound represented by Formula 2-a, had higher ionic conductivity and a higher ion transference number compared to Example 4, which used the compound represented by Formula 2-b. This is likely due to the fact that the highly electronegative fluorine delocalizes the anions of the adjacent sulfonylimide, thereby reducing the electron density of the sulfonylimide. As a result, the electrostatic attraction between lithium ions and the solid electrolyte is weakened, leading to the more efficient movement of dissociated lithium ions in the electrolyte.

[0706] Furthermore, referring to Table 1, it can be confirmed that the ionic conductivity and lithium-ion transference number of Examples 11 to 13 are superior to those of Comparative Examples 1 and 2. In particular, it can be confirmed that Example 13 is significantly superior to Comparative Examples 1 and 2. The compounds contained in the solid electrolytes of Examples 11 to 13 above contain an aromatic ring structure, wherein an alkoxy group is substituted at one carbon position of the benzene ring, and alkyl groups substituted with sulfonyl groups are located on both sides of the ortho position, thus having a lithium-affinity structure, resulting in excellent ionic conductivity and ion transference number. In particular, the compounds contained in the solid electrolyte of Example 13 have an ionic conductivity structure in which the sulfonylimide anion is fixed to the main chain, thus allowing dissociated lithium ions to move with higher efficiency. As a result, compared with Comparative Example 2 above, which does not contain an alkoxy group, and Comparative Example 1 above, which contains a conventional epoxy alkyl polymer, Examples 11 to 13 can have higher ionic conductivity and higher ion transference number.

[0707]

[0708] Referring to Table 2, it can be confirmed that Examples 9 and 10 exhibit higher levels of lithium-ion conductivity and ion transference number compared to Comparative Example 1. Furthermore, it can be confirmed that Examples 7 and 8 also exhibit higher levels of lithium-ion transference number compared to Comparative Example 1. The examples comprise ion-conducting polymers in which lithium-ion-affinity and low-electron-density sulfonamide anions are immobilized in the main chain. These ion-conducting polymers can move dissociated lithium ions in the electrolyte with higher efficiency, thus exhibiting higher ion conductivity and higher ion transference number performance compared to comparative examples containing conventional epoxyalkane polymers.

[0709] Furthermore, it was confirmed that Example 9, using a compound represented by Formula 2-c, had higher ionic conductivity and a higher ion transference number compared to Example 7, which used a compound represented by Formula 1-c. Example 10, with the addition of PETA, had a slightly lower lithium-ion transference number compared to Example 9, which did not contain the crosslinkable compound PETA. This is due to the fact that a network is formed between the double bonds via a free radical reaction, and is a result of the fact that by firmly forming a solid electrolyte structure, structural homogeneity is maintained while improving physical strength, such as tensile strength and tensile strain durability, without significantly reducing the ionic conductivity and transference number of lithium ions.

[0710] Experimental Example 4 - Evaluation of Battery Lifetime Properties

[0711] In a glove box, the polymer electrolyte membranes prepared in the various examples and comparative examples were immersed in an EC / PC (1:1 weight ratio) solvent. The polymer electrolyte membranes were then inserted between lithium foil electrodes (used as negative and positive electrodes) with a thickness of 200 μm in a battery case and stored at 60°C for about 12 hours to manufacture a coin battery containing electrode assemblies.

[0712] Using a charge / discharger at 25°C at 0.2 mA / cm 2 The coin cell battery was charged to its maximum current density for 1 hour and then discharged for 1 hour, constituting one cycle. This was repeated for three cycles. Subsequently, a charger was used at 1.0 mA / cm². 2 The coin cell battery was charged to its final charge-discharge cycle at a current density of 1.0 mA / cm² for 1 hour, then discharged for 1 hour, constituting one cycle. This cycle was repeated 400 times. Measurements were taken at a current density of 1.0 mA / cm². 2 The voltage generated during the first cycle, and also when the current density is 1.0 mA / cm². 2 The number of cycles when the generated voltage is 1.5 times that generated in the first cycle is shown in Table 3 below.

[0713]

[0714] Referring to Table 3, it can be confirmed that, compared with Comparative Examples 1 and 2, Examples 1 to 13 suppressed voltage rise, i.e., the battery life using the lithium metal anode was improved. In particular, in Examples 3 to 6, 9, 10, and 13, which used lithiated or lithium-containing ion-conducting polymers, it can be confirmed that the improvement in lifespan was significantly superior. This can be attributed to the improvement in ion conductivity and ion transport number, as well as the effect of suppressing the rise in electrode surface resistance and preventing dendrite formation on the surface of the lithium metal electrode caused by the compound containing the ion-conducting polymer according to the present invention.

Claims

1. A compound comprising a repeating unit represented by Formula 1, or a compound as its lithium salt: [Formula 1] In equation 1 above, X, Y, and Z are each independently selected from one or more of the following formulas a-1, b, and c-1. n is an integer from 1 to 100. q is an integer from 1 to 100. o is an integer from 0 to 100, and * indicates a connection point or terminal point between repeating units. [Formula a-1] [Formula b] [Formula c-1] In the above equations a-1, b, and c-1, R1, R2, and R3 are each independently hydrogen, halogen, -CN, -NO2, or substituted or unsubstituted C1-C. 10 Alkyl, substituted or unsubstituted C1-C 10 Alkoxy, substituted or unsubstituted C2-C 10 alkenyl, substituted or unsubstituted C2-C 10 Alkyne groups, -C(=O)R5, -P(=O)(OR5)2, -P(OR5)(OR6), -OP(=O)(OR5)(OR6), -S(=O)R5 or -S(=O)2R5, R4 is hydrogen or a substituted or unsubstituted C1-C. 10 alkyl, R5 and R6 are each independently hydrogen elements, substituted or unsubstituted C1-C. 10 Alkyl or substituted or unsubstituted C2-C 10 alkenyl, L1, L2, and L3 are each independently C1-C that are directly connected or substituted or unsubstituted. 10 Alkylene X1 and X2 are each independently hydrogen, halogen, -CN, -NO2, or substituted or unsubstituted C1-C. 10 Alkyl or substituted or unsubstituted C6-C 12 Aryl, m is an integer from 1 to 40, and p is an integer from 1 to 200.

2. The compound according to claim 1, wherein at least one of X, Y and Z comprises formula a-1 above.

3. The compound according to claim 1, wherein R2 and R4 are each independently C1-C5 alkyl groups.

4. The compound according to claim 1, wherein L1, L2 and L3 are each independently C1-C5 alkylene groups.

5. The compound according to claim 1, wherein X1 and X2 are each independently hydrogen or halogen elements.

6. The compound according to claim 1, wherein: n is an integer from 1 to 20; q is an integer from 1 to 20; o is an integer from 1 to 20; m is an integer from 1 to 10; and p is an integer from 1 to 50.

7. The compound according to claim 1, wherein the compound comprising the repeating unit represented by Formula 1 above is represented by Formula 1-a or Formula 1-b: [Equation 1-a] [Equation 1-b] In equations 1-a and 1-b above, n is an integer from 1 to 20. q is an integer from 1 to 20. o is an integer from 1 to 20.

8. The compound of claim 1, wherein the compound comprises at least one functional group selected from formulas d to g at at least one terminal site: [Formula d] [Form e] [Form f] [Formula g] In the above equations d to g, R7 is hydrogen or a substituted or unsubstituted C1-C. 10 alkyl, R8 to R 11 Each is independently a directly connected, substituted, or unsubstituted C1-C 10 Alkylene or -R 12 -OR 13 -, R 12 and R 13 Each is independently either directly connected or substituted or unsubstituted C1-C. 10 alkylene, and * indicates the binding position.

9. The compound according to claim 8, wherein: R7 is a C1-C6 alkyl group; R8 to R 11 Each is independently a directly linked, fluorine-substituted or unsubstituted C1-C6 alkylene group or -R 12 -OR 13 -;and R 12 and R 13 Each is an independent C1-C6 alkylene group that is directly connected or substituted or unsubstituted with fluorine.

10. The compound according to claim 8, wherein the compound is represented by formula 1-c: [Equation 1-c] In equation 1-c above, n is an integer from 1 to 20. q is an integer from 1 to 20. o is an integer from 1 to 20.

11. The compound of claim 1, wherein the lithium salt comprises a repeating unit represented by formula 2: [Equation 2] In equation 2 above, X, Y, and Z are each independently selected from one or more of the following formulas a-1, b, and c-1. n is an integer from 1 to 100. q is an integer from 1 to 100. o is an integer from 0 to 100, and * indicates a connection point or terminal point between repeating units. [Formula a-1] [Formula b] [Formula c-1] In the above equations a-1, b, and c-1, R1, R2, and R3 are each independently hydrogen, halogen, -CN, -NO2, or substituted or unsubstituted C1-C. 10 Alkyl, substituted or unsubstituted C1-C 10 Alkoxy, substituted or unsubstituted C2-C 10 alkenyl, substituted or unsubstituted C2-C 10 Alkyne groups, -C(=O)R5, -P(=O)(OR5)2, -P(OR5)(OR6), -OP(=O)(OR5)(OR6), -S(=O)R5 or -S(=O)2R5, R4 is hydrogen or a substituted or unsubstituted C1-C. 10 alkyl, R5 and R6 are each independently hydrogen elements, substituted or unsubstituted C1-C. 10 Alkyl or substituted or unsubstituted C2-C 10 alkenyl, L1, L2, and L3 are each independently C1-C that are directly connected or substituted or unsubstituted. 10 Alkylene X1 and X2 are each independently hydrogen, halogen, -CN, -NO2, or substituted or unsubstituted C1-C. 10 Alkyl or substituted or unsubstituted C6-C 12 Aryl, m is an integer from 1 to 40, and p is an integer from 1 to 200.

12. The compound according to claim 11, wherein the compound comprising the repeating unit represented by formula 2 above is represented by formula 2-a or formula 2-b: [Equation 2-a] [Equation 2-b] In equations 2-a and 2-b above, n is an integer from 1 to 20. q is an integer from 1 to 20. o is an integer from 1 to 20.

13. The compound of claim 11, wherein the compound comprises at least one functional group selected from formulas d to g at at least one terminal site of the terminal site: [Formula d] [Form e] [Form f] [Formula g] In the above equations d to g, R7 is hydrogen or a substituted or unsubstituted C1-C. 10 alkyl, R8 to R 11 Each is independently a directly connected, substituted, or unsubstituted C1-C 10 Alkylene or -R 12 -OR 13 -, R 12 and R 13 Each is independently either directly connected or substituted or unsubstituted C1-C. 10 alkylene, and * indicates the binding position.

14. The compound according to claim 13, wherein the compound comprising the repeating unit represented by formula 2 above is represented by formula 2-c: [Equation 2-c] In equation 2-c above, n is an integer from 1 to 20. q is an integer from 1 to 20. o is an integer from 1 to 20.

15. A complex comprising the compound of claim 1 and a lithium compound.

16. The complex according to claim 15, wherein the lithium compound is selected from one or more of the following substances: LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10 LiAlCl4, LiAlO4, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, lithium bis(fluorosulfonyl)imide (LiFSI) (LiN(SO2F)2), lithium bisperfluoroethanesulfonylimide (LiBETI) (LiN(SO2CF2CF3)2) and lithium (bis)trifluoromethanesulfonylimide (LiTFSI) (LiN(SO2CF3)2).

17. The complex according to claim 15, wherein the complex is represented by one or more of the following formulas: 3-a, 4-a, and 4-b [Equation 3-a] [Equation 4-a] [Equation 4-b] In equations 3-a, 4-a, and 4-b above, n is an integer from 1 to 20. q is an integer from 1 to 20. o is an integer from 1 to 20.

18. A solid electrolyte comprising one or more compounds selected from the compound of claim 1 and the complex of claim 15.

19. The solid electrolyte of claim 18, wherein the solid electrolyte further comprises a crosslinkable compound.

20. An all-solid-state battery comprising the solid electrolyte of claim 19.

21. A compound represented by the following formula A: [Formula A] In equation A above, R 21 R 22 and R 23 Each is independently hydrogen, halogen, substituted or unsubstituted C1-C 10 Alkyl, substituted or unsubstituted C1-C 10 Alkoxy, substituted or unsubstituted C2-C 10 Alkenyl or substituted or unsubstituted C2-C 10 alkynyl group, R 24 It is either hydrogen or substituted or unsubstituted C1-C 10 alkyl, L 21 and L 22 Each is independently either substituted or unsubstituted C1-C 10 Alkylene, -P(=O)(OR) 25 -, -(C=O)-, -(S=O)- or -S(=O)2-, X 21 and X 22 Each is independently a halogen element, -NH2, or phosphate ester (-OP(=O)(OR)). 25 )2), Nitrate esters (-ON(=O)(OR) 25 Toluenesulfonate (-OTs), sulfonate (-OS(=O)2R) 25 ) or carboxylic acid ester (-OC(=O)CH3), and R 25 C1-C, whether substituted or not 10 Alkyl, substituted or unsubstituted C2-C 10 Alkenyl or substituted or unsubstituted C2-C 10 Alkyne group.

22. The compound according to claim 21, wherein R 22 R 24 and R 25 Each is independently a C1-C5 alkyl group.

23. The compound according to claim 21, wherein L 21 and L 22 It is -S(=O)2-.

24. The compound according to claim 21, wherein X 21 and X 22 Each is an independent halogen element or -NH2.

25. The compound according to claim 21, wherein the compound represented by formula A is selected from one or more of the following formulas: Aa, Ab, and Ac. [Formula Aa] [Formula Ab] [Form Ac] 。 26. A complex comprising the compound of claim 21 and a lithium compound.

27. The complex according to claim 26, wherein the complex is represented by formula B: [Formula B] In equation B above, R 21 R 22 and R 23 Each is independently hydrogen, halogen, substituted or unsubstituted C1-C 10 Alkyl, substituted or unsubstituted C1-C 10 Alkoxy, substituted or unsubstituted C2-C 10 Alkenyl or substituted or unsubstituted C2-C 10 alkynyl group, R 24 It is either hydrogen or substituted or unsubstituted C1-C 10 alkyl, L 21 and L 22 Each is independently either substituted or unsubstituted C1-C 10 Alkylene, -P(=O)(OR) 25 -, -(C=O)-, -(S=O)- or -S(=O)2-, X 21 and X 22 Each is independently a halogen element, -NH2, or phosphate ester (-OP(=O)(OR)). 25 )2), Nitrate esters (-ON(=O)(OR) 25 Toluenesulfonate (-OTs), sulfonate (-OS(=O)2R) 25 ) or carboxylic acid ester (-OC(=O)CH3), R 25 C1-C, whether substituted or not 10 Alkyl, substituted or unsubstituted C2-C 10 Alkenyl or substituted or unsubstituted C2-C 10 alkynyl group, and Y - It is selected from one or more of the following substances: halide anions, BF4 - ClO4 - AlCl4 - AlO4 - PF6 - CF3SO3 - CH3CO2 - CF3CO2 - AsF6 - SbF6 - CH3SO3 - bis(fluorosulfonyl)imide (FSI) - (N(SO2F)2) - ), bis(perfluoroethanesulfonyl)imide (BETI) (N(SO2CF2CF3)2 - ) and (bis)trifluoromethanesulfonylimide (TFSI) (N(SO2CF3)2 - ).

28. The complex according to claim 26, wherein the complex is one or more selected from the formula Ba, Bb and Bc: [Formula Ba] [Formula Bb] [Formula Bc] 。 29. A polymer comprising repeating units derived from the compound of claim 21, repeating units derived from the complex of claim 26, or a combination thereof.

30. The polymer of claim 29, wherein the repeating unit derived from the compound of claim 21 is represented by the following formula Wa or Wb: [Formula Wa] [Formula Wb] In the above equations Wa and Wb, n is an integer from 1 to 300, and * indicates the connection point between repeating units.

31. The polymer of claim 29, wherein the repeating unit derived from the composite of claim 26 is represented by the following formula Xa or Xb: [Form Xa] [Formula Xb] In the above equations Xa and Xb, Y - It is selected from one or more of the following substances: halide anions, BF4 - ClO4 - AlCl4 - AlO4 - PF6 - CF3SO3 - CH3CO2 - CF3CO2 - AsF6 - SbF6 - CH3SO3 - bis(fluorosulfonyl)imide (FSI) - (N(SO2F)2) - ), bis(perfluoroethanesulfonyl)imide (BETI) (N(SO2CF2CF3)2 - ) and (bis)trifluoromethanesulfonylimide (TFSI) (N(SO2CF3)2 - ), n is an integer from 1 to 300, and * indicates the connection point between repeating units.

32. The polymer of claim 29, wherein the combination of the repeating unit derived from the compound of claim 21 and the repeating unit derived from the complex of claim 26 is represented by the following formula Y or Z: [Formula Y] [Form Z] In the above equation, Y and Z, Y - It is selected from one or more of the following substances: halide anions, BF4 - ClO4 - AlCl4 - AlO4 - PF6 - CF3SO3 - CH3CO2 - CF3CO2 - AsF6 - SbF6 - CH3SO3 - bis(fluorosulfonyl)imide (FSI) - (N(SO2F)2) - ), bis(perfluoroethanesulfonyl)imide (BETI) (N(SO2CF2CF3)2 - ) and (bis)trifluoromethanesulfonylimide (TFSI) (N(SO2CF3)2 - ), n and m are each independent integers from 1 to 300, and * indicates the connection point between repeating units.

33. A solid electrolyte comprising the polymer of claim 29.

Citation Information

Patent Citations

  • Ionically conductive composite hydrophilic membrane

    JP1985069140A

  • Apparatus and method for transmitting data in multiple antenna system

    KR1020230057976A

  • Control method of node for minimizing power consumption by flexibly setting scan window

    KR1020230057984A

  • Apparatus and method for detecting fraud automatic response service

    KR1020230094880A